Counterflow premixed ammonia/air flame extinction limits at elevated temperatures and pressures - James F. Stevens; Rouzhou Fang; Benjamin Rees; Ian Pichs; Shannon Dunn; Paul Papas; Lance Smith; Chih-Jen Sung (Fuel, 2027)

Coordination versus capacity: quantifying the resilience contribution of airport operations centers - Madison Smith; Savannah Morgan; Joshua Trump; Benjamin Trump; Robert Horton (Environment Systems and Decisions, 2026)

Blue beats green: Agonistic interactions between Atlantic blue crabs and European green crabs in the Gulf of Maine - Samantha A. Smith; Reuben P. Siegel; Laura C. Crane; Kayla B. Cheney; Benjamin C. Gutzler; Jaret S. Reblin; Jason S. Goldstein; Christopher D. Wells (Journal of Experimental Marine Biology and Ecology, 2026)

Concurrent Phosphite Oxidation and Adenosine Phosphorylation Under Prebiotic Evaporative Conditions - Maheen Gull; Judit E. Šponer; Harold A. Cruz; Edoardo J. Gallazi; Benjamin Smith; Scott A. McCallum; Karyn L. Rogers; Matthew A. Pasek (Journal of Molecular Evolution, 2026)

Blue and green: A portrait of two portunoidea crabs from away and their interactive effects on catch - Guillaume Marchessaux; Laura C. Crane; Benjamin C. Gutzler; Samantha A. Smith; Gianluca Sarà; Jason S. Goldstein (Marine Environmental Research, 2026)

How narratives construct wickedness in mission-oriented innovation policy problems - Benjamin D Smith (Environmental Innovation and Societal Transitions, 2026)

Using interactive education materials to empower children to be future consumers of alternative proteins: A randomised active-controlled trial - Aimee E. Pink; Kum Seong Wan; Siti Amelia Juraimi; Mansi Bhatnagar; Jolene Chee; Hui Si Oh; Joseph Simons; Pey Sze Teo; Florence Sheen; Mary F-F Chong; Benjamin P.C. Smith; Anna Fogel (Appetite, 2026)

An Optimized Method for Efficient Conjugal Transfer in Flavobacterium covae - Stacey LaFrentz; Hannah Smith; Benjamin R. LaFrentz; Jake Tatum; Miles D. Lange; Mark R. Liles (Journal of Fish Diseases, 2026)
The fish pathogen Flavobacterium covae causes significant mortality and there is a need to better understand virulence factors that contribute to its pathogenesis. Few highly virulent F. covae strains may be genetically manipulated with existing conjugal transfer methods, therefore the aim of this study was to increase conjugal transfer efficiency and broaden the range of recipient F. covae strains. Different parameters were evaluated for improvement of F. covae conjugal transfer efficiency using plasmid pCP23, and improved conjugal transfer was observed by altering the Escherichia coli donor strain, media and donor to recipient cell ratios. An optimized method including these changes was compared to a previously published conjugation method, which enabled conjugal transfer of pCP23 into seven of eleven F. covae strains in contrast to only four strains with the previous method. Additionally, the use of the optimized method resulted in orders of magnitude increases in conjugal transfer efficiency for multiple F. covae strains relative to the previous method ( p 6 transconjugants per 10 9 recipient cells. This optimized conjugation method will facilitate a better understanding of the molecular mechanisms of pathogenesis in virulent F. covae strains.

Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Advancing conservation through virtual livestock fencing - Drew E. Bennett; Travis Brammer; Jerod A. Merkle; Kurt T. Smith; Shawn Regan; Temple Stoellinger; Arthur Middleton; Kristin Barker; Jacob P. Hochard; Patrick E. Lendrum; Erin Welty; Craig Benjamin; et al. (Biological Conservation, 2026)

Restoring surf and turf: Transferable lessons between marine and terrestrial restoration - Trevyn A. Toone; Emilee D. Benjamin; Julie Larson; Mary-Margaret S. McKinney; James C. Russell; Carter Smith; Y. Stacy Zhang (Biological Conservation, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Deciphering phosphorus dynamics in impacted river systems using phosphate oxygen and lead isotope analysis - Daren C. Gooddy; Andrew M. Tye; Andrew C. Smith; Simon R. Chenery; Benjamin JW. Surridge (Applied Geochemistry, 2026)

Whole‐Genome‐Sequencing Reveals Demographic History and Patterns of Parallel Adaptive Evolution in Indo‐Pacific Bottlenose Dolphins ( Tursiops aduncus ) Across Coastal Australian Seascapes - Svenja M. Marfurt; Adrien Tran Lu Y; Benjamin Dauphin; Manuela R. Bizzozzero; Masaomi Hatakeyama; Delphine B. H. Chabanne; Simon J. Allen; Felix Smith; Guido J. Parra; Michael Krützen (Molecular Ecology, 2026)
Understanding how demographic dynamics interact with environmental heterogeneity is central to explaining patterns of genomic variation in the marine realm. Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) occur along most of the Australian coastline, from tropical to temperate waters, encompassing pronounced differences in temperature, salinity, chlorophyll‐a concentration and ocean currents. Using whole‐genome sequencing of individuals covering this range, we examined population genetic structure and adaptive divergence at a continental scale. Genome‐wide variation mirrored geographic patterns, consistent with a common origin in the north, followed by two independent stepping‐stone‐like colonization patterns along the eastern and the western coastlines from north to south. In contrast, putatively adaptive loci clustered individuals by tropical waters regardless of geographic distance, indicating strong parallel adaptation in tropical habitats. Candidate loci were enriched for functions related to metabolism and ion transport, with some mapping to genes with regulatory functions. Additional signals potentially suggest involvement of neuronal pathways, consistent with adaptation in a highly social and cognitively advanced marine mammal. Our results highlight the complex interplay between demographic history and selection and suggest tropical–temperate, potentially ecotype‐like differentiation across Australian waters. In the face of accelerating climate change, recognizing such adaptive structuring is critical for preserving evolutionary potential. Incorporating adaptive genomic information into conservation planning, alongside neutral genetic data, will be essential for anticipating population responses to future environmental change and for identifying biologically meaningful conservation units.

Ecology and mechanisms of brood raiding of Iridomyrmex by the thermophilic ant, Melophorus anderseni - Benjamin D. Hoffmann; Sara Hu; Adrian A. Smith; Andrew V. Suarez; Terry McGlynn (Insectes Sociaux, 2026)
Melophorus anderseni is a thermophilic ant species that nests near colonies of Iridomyrmex on which it conducts brood raids. We examined its colony founding behavior and foraging ecology to evaluate possible mechanisms that may facilitate interspecific nest raiding, as well as determine if it is a parasite or specialist predator. Specifically, we (1) examined colony establishment and survival, (2) patterns of worker activity (walking speed, foraging and raiding behavior), and (3) compared cuticular hydrocarbon profiles of M. anderseni and I. reburrus workers. Following nuptial flights, M. anderseni queens established colonies in clusters around I. reburrus colonies, with an average distance to the nearest Iridomyrmex nest of 133.1(± 8.9) cm (range 25 to 650 cm). The average number of M. anderseni queens per Iridomyrmex nest entrance was 8.4 (± 1.9), and the average distance to the nearest M. anderseni neighbor was 44.9 (± 5.3) cm (range 10 to 233 cm). Queen survival was lower in clusters that were farther from the nearest I. reburrus nest or to other M. anderseni queens. Iridomyrmex reburrus activity was negatively related to soil temperature, with no activity occurring above 50 °C. In contrast, M. anderseni activity was positively related to temperature with peak activity occurring just above 50 °C. Melophorus anderseni worker activity commenced when soil temperatures exceeded 37.4 °C, and activity increased until mid-day. Activity ceased in the afternoon at temperatures lower than that for activity commencement, on average at 36.7 °C. Activity of M. anderseni at I. reburrus nests followed that of activity at M. anderseni nests. Workers of M. anderseni had an average foraging duration of 63 s and a mean foraging distance of 249 cm. Of the 49 foragers followed, 42 (86%) entered an I. reburrus nest, and 32 (76.2%) of those entered the closest nest entrance. Of the 1,444 observations of M. anderseni exiting an I. reburrus nest, they stole an item in 122 (8.4%) instances, with 117 (95.9%) of these items being brood. Additionally, workers of M. anderseni had faster running speeds (mean 9.72 cm/s, peak 18 cm/s) than I. reburrus workers (7.05 cm/s). On average, the speed of M. anderseni exiting an I. reburrus nest was more than twice the speed of I. reburrus. Extracts of I. reburrus and M. anderseni worker cuticular hydrocarbon profiles were qualitatively identical in that no compounds were unique to either species. Saturated hydrocarbons with chain lengths between 25 and 29 carbons comprised the majority of hydrocarbons found on the cuticle of both species. The relative abundances of compounds within the profiles of both species were also similar. In contrast, two sympatric Iridomyrmex and Melophorus species shared very few compounds with I. reburrus and M. anderseni . During all observations of the M. anderseni nests, no I. sanguineus workers were observed within or exiting the nest entrance, indicating that stolen brood had been consumed. Our results support that M. anderseni specializes on brood raiding from I. reburrus nests, and this raiding is for predation, not dulosis. Both behavior (running speed) and chemical mimicry are likely used in combination to facilitate this specialized foraging. Additional research is still needed to determine the source (e.g. genetic versus environmental) of M. anderseni’s hydrocarbon profiles, and if geographic variation in host use and chemical mimicry exists.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Tax system analysis for deep-sea mining in Norway: A genetic algorithm approach - Verena Hagspiel; Maxime Lesage; Farida Mustafina; Benjamin Rike; Sander Skonhoft; Jonatan Smith (Resources Policy, 2026)

Shaping future diets: Examining capabilities, opportunities and motivations to increase acceptance of alternative proteins in families - Siti Amelia Juraimi; Florence Sheen; Anna Fogel; Mary F.-F. Chong; Benjamin P.C. Smith; Aimee E. Pink (Food Quality and Preference, 2026)

Identifying phase-specific environmental drivers of drought-induced vegetation dynamics via spectral Proxies - Nuwanthi Arampola; Rachid Oucheikh; Belinda Medlyn; Samuel Hislop; Brendan Choat; Pengxiang Zhao; Benjamin Smith; Ali Mansourian (Environmental Modelling & Software, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Substituting sitting with standing and walking in free-living conditions improves daily glucose concentrations in South Asian adults living with overweight/obesity - Kamalesh C. Dey; Julia K. Zakrzewski-Fruer; Lindsey R. Smith; Rebecca L. Jones; Benjamin D. Maylor; Thomas E. Yates; Daniel P. Bailey (European Journal of Applied Physiology, 2026)
Background Controlled laboratory studies have demonstrated that breaking up sitting can reduce postprandial glucose in South Asian adults. This study examined the effects of substituting sitting with standing and walking on interstitial glucose in South Asian individuals under free-living conditions. Methods South Asian adults ( n = 14 [50% male]; body mass index 26.5 ± 0.8 kg·m −2 ) aged 41 ± 3 years completed two, 4-day regimens in a counter-balanced order: (1) SIT (restrict walking and standing to ≤ 1 h/day each) and (2) SITless (substitute ≥ 5 h/day of sitting with ≥ 3 h of standing and ≥ 2 h of walking, and interrupt sitting every 30 min). Interstitial glucose was measured using Flash glucose monitoring. Sitting and physical activity were measured with the activPAL3. Outcomes were compared between regimens using linear mixed models. Results Interstitial glucose net incremental area under the curve (iAUC) for waking hours was lower by − 9.2 mmol L −1 ·16 h −1 (95% Confidence Interval [CI]: − 18.1, − 0.3) in SITless than SIT ( p = 0.04), while lunch postprandial glucose iAUC was significantly lower by -1.0 mmol L −1. 2 h −1 (95% CI − 1.8, 0.2) in SITless ( p = 0.02). There were no significant differences in other 24 h or 16 h glucose metrics ( p ≥ 0.06). Compared to SIT, sitting was lower by − 3.6 h/day (95% CI − 4.9, − 2.3) in SITless ( p < 0.01). Standing and stepping time were higher by 1.9 h/day (95% CI 0.6, 3.2) and 1.6 h/day (95% CI 1.2, 2.1) in SITless ( p ≤ 0.01). Conclusions Substituting sitting with standing and walking under free-living conditions can be used to effectively attenuate glycaemia during waking hours, but not across 24 h, in South Asian adults. Clinical trial registration NCT04645875..

Impacts of Tree Allometry on Structure, Composition, Functioning and Competitive Interactions in Savanna Ecosystems on the Northern Australian Tropical Transect - Prashant Paudel; Stefan Olin; Mark Tjoelker; Mikael Pontarp; Daniel Metcalfe; Benjamin Smith (Journal of Biogeography, 2026)
Aim Allometric relationships, which describe plant growth patterns shaped by environmental conditions, reflect functional trade‐offs and represent key functional traits that optimise adaptation, resource acquisition, stress tolerance and competition. Here, we assess how these allometric relationships and associated functional trade‐offs drive ecosystem structure, functioning and competitive interactions between plant functional types (PFTs) in savanna ecosystems. Location Rainfall gradient, North Australian Tropical Transect (NATT), Australia. Time Period 1901–2022. Taxon Tree species of Northern Australia. Methods Using quantile regression, we established adaptive allometric relationships among diameter at breast height, tree height, crown radius and crown volume. These relationships were integrated into a dynamic vegetation model to simulate tree growth and competitive interactions in local patches across the broader savanna landscape. The model was validated using observed biomass, height, leaf area index and productivity data from six flux tower sites across the NATT. A neighbour removal experiment was conducted to analyse PFT performance under varying competitive pressure, expressed as a competitive index. Results The results demonstrate that incorporating adaptive allometric relationships improved the model's ability to represent vegetation dynamics and productivity. Tall Eucalyptus PFTs exhibited competitive dominance in high rainfall areas, while Acacia and other deciduous species thrived under drier conditions. The neighbour removal experiment revealed that competition strongly influenced PFT performance, with carbon mass production varying significantly between stand types. Tall Eucalyptus PFTs showed little response to neighbour removal, while other PFTs benefitted strongly from neighbour removal. The competitive index of PFTs increased significantly with rainfall, indicating stronger competition under wetter conditions. Main Conclusions Our findings suggest that savanna ecosystems are shaped by complex interactions between growth conditions, functional traits and adaptive strategies for coping with competition and stress. These interactions are reflected in allometric relationships and the associated trade‐offs in plant growth strategies, which vary across different rainfall gradients.

Thirty years of arboreal wildlife trends in an African rainforest under evolving threats and researchers' presence - Bastien Dehaudt; Ruksan Bose; Jean Jacques Avoto; Stephanie Brittain; Tom Bruce; Emily K. Chen; Francis A. Forzi; Britta D. Hardesty; Kimberly M. Holbrook; Aaron M. Lamperti; V. Thomas Parker; John R. Poulsen; et al. (Biological Conservation, 2025)

Light attenuation due to preferential orientation of particles in waves and shear flow: Idealized modeling for bacteria, algae, and microplastics - Samuel T. Salemink‐Harry; Benjamin J. Smith; Hilary A. Dugan; Jennifer A. Franck; Till J.W. Wagner; Lucas K. Zoet; Grace M. Wilkinson; Nimish Pujara (Limnology and Oceanography, 2025)
Particles are a key component of aquatic light climate due to their attenuation of light. Near the water surface, waves and sheared currents can induce a preferential orientation of nonspherical particles that alters their inherent optical properties and the associated light attenuation. This modeling study focuses on how particle shape, and the corresponding preferential orientation, impacts the light climate in an aquatic environment. We assume aquatic particles, such as bacteria, algae, and microplastic pollutants, are optically homogeneous spheroids that move with the flow. The model computes their preferential orientations within the upper water column in flow driven by linear water waves and sheared currents. This is combined with the anomalous diffraction optical approximation to examine the effect of particle orientation on the beam attenuation coefficient. We find that the preferential orientation by waves and shear tends to increase the projected area of the spheroid compared to random (isotropic) orientation. This has particle size‐dependent effects on light attenuation: for particles comparable in size and shape to algae or microplastics, the preferential orientation corresponds to an increase of 10–25% in the beam attenuation coefficient, whereas there is a decrease of 10–20% in the beam attenuation coefficient for smaller particles comparable in size to bacteria. Overall, our results reveal how preferential orientation of nonspherical particles by waves and currents can impact light climate in the upper water column.

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Think globally, barcode locally: nine years of macrofungi sampling reveals extensive biodiversity at the ordway-swisher biological station, a subtropical site in Florida - Marcos V. Caiafa; Laurel Kaminsky; Rosanne Healy; Leanne P. Sheffer; C. Benton Willis; Katy Deitz; Brantlee S. Richter; Benjamin R. Lemmond; David Borland; Bitty A. Roy; Heather A. Dawson; Carolyn A. Delevich; et al. (Fungal Biology, 2025)

A new multituberculate (Mammalia, Allotheria) from the Lulworth Formation (Cretaceous, Berriasian) of Dorset, England - Benjamin T. Weston; Steven C. Sweetman; Jake Kean; Charles Wood; David M. Martill; Roy E. Smith (Proceedings of the Geologists' Association, 2025)

Geographic variation in stable isotope ratios of subtropical American eel (Anguilla rostrata) - Michael E. Curtis; Dean Hendrickson; Adam Cohen; Melissa Casarez; Stephen Curtis; Nathan G. Smith; Benjamin D. Walther (Environmental Biology of Fishes, 2025)
American eel ( Anguilla rostrata ) life history strategies and food web interactions are highly variable in temperate climates but not well understood in sub-tropical hydrologic systems. Intraspecific variability in isotopic niche breadth and overlap can have major implications for species of conservation concern by revealing dietary plasticity of populations across varied habitats. Muscle tissue stable isotope ratios of carbon (δ 13 C), nitrogen (δ 15 N), and sulfur (δ 34 S) were analyzed to assess geographic variance in recent trophic histories within and among American eels collected in tributaries of the northwestern Gulf of Mexico and to quantify isotopic niche breadths and overlaps of capture groups. A total of eight specimen groupings were designated according to the riverine and coastal basins where they were collected, with one group comprised of only individuals caught within a wastewater treatment plant. Univariate analyses revealed highly variable isotopic ratios within and between groups. The probability of groups being found in the niche region of another group was low, with only six instances in which the probability of overlap was over 10%. The Colorado (C) group showed the highest probability of overlap of any group, being found in 86.57% of the Brazos-San Jacinto (B-SJ) group’s niche region. Collectively, these results illustrate the high degree of geographic variation in isotope ratios within and between regional habitats in an understudied portion of the species’ range.

Testing the effectiveness of education to increase acceptance of alternative proteins in children: A randomised control trial - Florence Sheen; Siti Amelia Juraimi; Wan Kum Seong; Joseph Simons; Pey Sze Teo; Myat Min; Petrus Bonang; Kristabel Khoo; Benjamin P.C. Smith; Mary F-F. Chong; Anna Fogel; Aimee E. Pink (Appetite, 2025)

Urbanisation Facilitates Intrapopulation Dietary Niche Diversity in a Generalist Carnivore - Tal Caspi; Emily Sit; Monica G. Serrano; Stevi L. Vanderzwan; Katie A. Smith; William Merkle; Deb Campbell; Benjamin N. Sacks (Ecology Letters, 2025)
The niche variation hypothesis predicts that members of generalist species are specialists, and that the degree of individual specialisation correlates positively with resource diversity. Urban landscapes are highly heterogeneous in resource distribution; therefore, we predicted urbanisation would be associated with narrower individual dietary niches and greater differentiation among individuals of generalist species. We used stable isotope analysis to compare diets of urban and nonurban coyote ( Canis latrans ) populations in San Francisco and Marin County, California, USA. Urban coyotes had dietary niches nearly three times narrower than nonurban coyotes and greater among‐individual variation in isotope values. Within‐individual differences explained 18% of total δ 13 C variation in urban coyotes compared to 58% in nonurban coyotes, and 34% versus 44% of δ 15 N variation, indicating stronger individual specialisation in the urban population. Our findings suggest urbanisation facilitates intrapopulation dietary niche diversity by spatially structuring foraging, highlighting the role of human activity in promoting ecological diversification.

Tissue-specific energetics of the invasive Asian shore crab Hemigrapsus sanguineus throughout its range and through time - Blaine D. Griffen; Laura S. Fletcher; Tanner C. Reese; Michele F. Repetto; Nanette Smith; Carter K. Stancil; Benjamin J. Toscano (Oecologia, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Drivers of Regional Variability in Producer and Consumer Stable Isotope Values (δ13C and δ15N) Within Turtle Grass-Dominated Meadows Across the Northern Gulf of Mexico - Christian Todd Hayes; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Correia; M. Zachary Darnell; Kevin S. Dillon; Bradley T. Furman; Margaret O. Hall; Charles W. Martin; Ashley M. McDonald; Delbert L. Smee; Samantha M. Smith; et al. (Estuaries and Coasts, 2025)

Toxicity of the water-soluble polymer PVP is dependent on molecular weight and feed concentration for a freshwater model species - Eve C. Tarring; Charlotte Robison-Smith; Angel D. Ceballos-Ramirez; Isabelle Durance; Michael J. Harbottle; Jo Cable; Benjamin D. Ward (Science of The Total Environment, 2025)

World Trade Center response activities and cognitive health: A moderated mediation study of the role of surgical/nuisance dust mask usage - Yuan Yang; Jaymie Meliker; Lauren L. Richmond; Frank D. Mann; Minos Kritikos; Dylan M. Smith; Tesleem Babalola; Melissa A. Carr; Benjamin J. Luft; Sean A.P. Clouston (NeuroToxicology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

“It's most likely gonna be the future”: A qualitative study exploring child and parent perceptions of alternative proteins - Nandini Anant; Arunika Pillay; Siti Amelia Juraimi; Florence Sheen; Anna Fogel; Mary F-F. Chong; Benjamin P.C. Smith; Aimee E. Pink (Appetite, 2025)

Adaptive capacities of inland fisheries facing anthropogenic pressures - Gretchen L. Stokes; Samuel J. Smidt; Emily L. Tucker; Matteo Cleary; Simon Funge-Smith; John Valbo‐Jørgensen; Benjamin S. Lowe; Abigail J. Lynch (Global Environmental Change, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Correction to: Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Incorporating Singaporean habits and practices for cosmetics and personal care products into a global consumer aggregate exposure model - Siti Amelia Juraimi; Cesar Scrochi; Jonathan Lok; Anne Marie Api; Benjamin P.C. Smith (Regulatory Toxicology and Pharmacology, 2025)

Baseline matters: Challenges and implications of different marine heatwave baselines - Kathryn E. Smith; Alex Sen Gupta; Dillon Amaya; Jessica A. Benthuysen; Michael T. Burrows; Antonietta Capotondi; Karen Filbee-Dexter; Thomas L. Frölicher; Alistair J. Hobday; Neil J. Holbrook; Neil Malan; Pippa J. Moore; et al. (Progress in Oceanography, 2025)

Sediment, light, and interspecific interactions have strong but independent species-specific effects on two dominant coral reef macroalgae - Shalanda R. Grier; Benjamin A. Hà; Emily R. Ryznar; Lauren L. Smith; Peggy Fong (Marine Biology, 2025)

Identification and epidemiological analysis of a putative novel hantavirus in Australian flying foxes - Craig S. Smith; Darren J. Underwood; Anita Gordon; Michael J. Pyne; Anna Smyth; Benjamin Genge; Luke Driver; David G. Mayer; Jane Oakey (Virus Genes, 2025)
In July 2017, an investigation into the cause of neurological signs in a black flying fox ( Pteropus alecto , family Pteropodidae ) identified a putative novel hantavirus (Robina virus, ROBV, order Bunyavirales , family Hantaviridae , genus Mobatvirus ) in its brain. Analysis of the evolutionary relationship between other hantaviruses using maximum-likelihood, a systematic Bayesian clustering approach, and a minimum spanning tree, all suggest that ROBV is most closely related to another Mobatvirus , Quezon virus, previously identified in the lung of a Philippine frugivorous bat ( Rousettus amplexicaudatus , also family Pteropodidae ). Subsequently, between March 2018 and October 2023, a total of 495 bats were opportunistically screened for ROBV with an experimental qRT-PCR. The total prevalence of ROBV RNA detected in Pteropus spp. was 4.2% (95% CI 2.8–6.4%). Binomial modelling identified that there was substantial evidence supporting an increase ( P = 0.033) in the detection of ROBV RNA in bats in 2019 and 2020 suggesting of a possible transient epidemic. There was also moderate evidence to support the effect of season ( P = 0.064), with peak detection in the cooler seasons, autumn, and winter, possibly driven by physiological and ecological factors similar to those already identified for other bat-borne viruses. This is Australia’s first reported putative hantavirus and its identification could expand the southern known range of hantaviruses in Australasia.

Integrating process-based vegetation modelling with high-resolution imagery to assess bark beetle infestation and land surface temperature effects on forest net primary productivity - Haidi Abdullah; Elnaz Neinavaz; Roshanak Darvishzadeh; Margarita Huesca; Andrew K. Skidmore; Mats Lindeskog; Benjamin Smith; Marco Heurich; Rainer Steinbrecher; Marc Paganini (Remote Sensing Applications: Society and Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

Assessing nanotoxicity of food-relevant particles: A comparative analysis of cellular responses in cell monolayers versus 3D gut epithelial cultures - Archana Gautam; Hui Kheng Lim; Jasmine Jia’En Li; Christopher Owen Hughes; Calvin Wee Sing Yeo; Moumita Rakshit; David Ian Leavesley; Michelle Jing Sin Lim; Joseph Choon Wee Tan; Li Yi Tan; Joanne Sheot Harn Chan; Benjamin Paul Chapman Smith; et al. (Food and Chemical Toxicology, 2024)

Investigation of geochemically induced permeability alteration in geothermal reservoirs and its implications for sustainable geothermal energy production - Taylor Smith; Adedapo N. Awolayo; Stephen E. Grasby; Benjamin M. Tutolo (Applied Geochemistry, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Factors influencing variation in reproduction in invasive species: a case study of the Asian shore crab Hemigrapsus sanguineus - Blaine D. Griffen; Mikayla Bolander; Laura S. Fletcher; Johanna Luckett; Michele F. Repetto; Nanette Smith; Carter Stancil; Benjamin J. Toscano (Biological Invasions, 2024)
Reproductive success is a strong determinant of invasive species success. It is common for studies on invasive species to assess reproduction by measuring size-specific fecundity and scaling this up using population size or densities. Yet, reproductive success is influenced by numerous factors that are not accounted for in such calculations. We examined the influence of several factors on fecundity (clutch size) and egg size in the Asian shore crab Hemigrapsus sanguineus , including body size, spatial variation throughout the invaded range, season, fertilization success, brood loss, and diet. We show that all of these factors influence reproduction simultaneously within the invaded North American range of this species, though the relative importance of these different factors varied across sites or sampling times. Our study demonstrates that numerous factors may influence the reproductive success of invasive species and that studies that rely on fecundity measured at a single place and time, or that ignore factors such as offspring quality or brood loss, may provide a skewed picture of reproduction, and thus of potential invasive success.

High-resolution urban climate simulations for heat and health applications in Philadelphia - Benjamin Le Roy; Keith W. Dixon; Dennis Adams-Smith (Urban Climate, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

The development of an interactive platform to educate children on alternative proteins - Aimee E. Pink; Siti Amelia Juraimi; Arunika Pillay; Liang Ze Wong; Joseph Simons; Florence Sheen; Anna Fogel; Mary F-F Chong; Benjamin P.C. Smith; Kristabel Khoo; Petrus Bonang; Myat Min (Appetite, 2024)

Genetic structure of restored Brook Trout populations in the Southern Appalachian Mountains indicates successful reintroductions - Rebecca J. Smith; David C. Kazyak; Matt A. Kulp; Barbara A. Lubinski; Benjamin M. Fitzpatrick (Conservation Genetics, 2024)

Isolation, small population size, and management influence inbreeding and reduced genetic variation in K’gari dingoes - Susan M. Miller; Linda Behrendorff; Benjamin L. Allen; Rose L. Andrew; Guy Ballard; J. William O. Ballard; Kylie M. Cairns; Gabriel C. Conroy; Peter J. S. Fleming; Catherine E. Grueber; Jane Oakey; Deane A. Smith; et al. (Conservation Genetics, 2024)
Small island populations are vulnerable to genetic decline via demographic and environmental stochasticity. In the absence of immigration, founder effects, inbreeding and genetic drift are likely to contribute to local extinction risk. Management actions may also have a greater impact on small, closed populations. The demographic and social characteristics of a species can, however, delay the impact of threats. K’gari, a ~ 1 660 km 2 island off the Australian east coast and UNESCO World Heritage Site (Fraser Island 1842–2023), supports an isolated population of approximately 70–200 dingoes that represent an ideal opportunity to explore the small island paradigm. To examine temporal and spatial patterns of genetic diversity in this population we analysed single nucleotide polymorphism (SNP) genotype data (72 454 SNPS) for 112 K’gari dingoes collected over a 25-year period (1996 to 2020). Genetic diversity was lower in K’gari dingoes than mainland dingoes at the earliest time point in our study and declined significantly following a management cull in 2001. We did not find any spatial genetic patterns on the island, suggesting high levels of genetic connectivity between socially discrete packs. This connectivity, combined with the social structure and behaviour of dingoes, may act in concert to buffer the population from the impacts of genetic drift in the short term. Nevertheless, a general decline in genetic variation via inbreeding and drift has occurred over the past 20 years which we suggest should be considered in any future management planning for the population. Monitoring patterns of genetic variation, together with a clearer understanding of the social ecology of K’gari dingoes, will aid in the development of measurable genetic targets set over ecologically meaningful timelines, and help ensure continued survival of this culturally important population.

What makes a habitat a home? Habitat associations of juvenile European sea bass, Dicentrarchus labrax , in estuarine nurseries - Howard A. Freeman; Leanne J. Hepburn; Martin I. Taylor; Ewan Hunter; Alex J. Dumbrell; Benjamin H. Gregson; Albert J. Smith; Aaron Lamphierre; Tom C. Cameron (Journal of Fish Biology, 2024)
Selection of nursery habitats by marine fish, such as European sea bass ( Dicentrarchus labrax ), is poorly understood. Identifying and protecting the full range of juvenile nursery habitats is vital to supporting resilient fish populations and economically important fisheries. We examined how the condition, stomach fullness, and diet of juvenile European sea bass, along with their abundance, differ at high or low tide between the following estuarine habitats: saltmarsh, oyster reefs, shingle, sand, and mud edge habitats. Using a combination of fyke and seine netting we found no difference in sea bass abundance or condition across high‐tide habitats, suggesting that rather than differentially selecting between them, juvenile sea bass use all available shallow habitats at high tide. Stomach fullness was significantly higher on saltmarsh and sand compared to mud, and thus these habitats may support better foraging. Dietary DNA metabarcoding revealed that sand and saltmarsh diets mostly comprised Hediste polychaetes, whereas zooplanktonic taxa dominated diets over mud. At low tide, sea bass abundance was highest in shingle and oyster reefs, where stomach fullness and condition were lowest. This may indicate a potential trade‐off between using habitats for foraging and refuge. Although sea bass abundance alone does not capture productivity, the high abundance across all estuarine habitats at high tide suggests that it is important to consider the protection of a mosaic of interconnected habitats to support nursery functions rather than focus on individual habitat types.

Detection of polyvinylpyrrolidone in Daphnia magna: Development of a refractive index quantification method for water-soluble polymers in aquatic organisms - Eve C. Tarring; Charlotte Robison-Smith; Jo Cable; Isabelle Durance; Michael Harbottle; Benjamin D. Ward (Science of The Total Environment, 2024)

Corrigendum to “A class of their own? Water-soluble polymer pollution impacting a freshwater host-pathogen system” [Sci. Total Environ. 907 (2024) 168086] - Charlotte Robison-Smith; Numair Masud; Eve C. Tarring; Benjamin D. Ward; Jo Cable (Science of The Total Environment, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Modelling changes in vegetation productivity and carbon balance under future climate scenarios in southeastern Australia - Bin Wang; Benjamin Smith; Cathy Waters; Puyu Feng; De Li Liu (Science of The Total Environment, 2024)

Pathways from research to sustainable development: Insights from ten research projects in sustainability and resilience - Anna Scaini; Joseph Mulligan; Håkan Berg; Albert Brangarí; Vera Bukachi; Sebastian Carenzo; Da Chau Thi; Colin Courtney-Mustaphi; Anneli Ekblom; Hanne Fjelde; Mathias Fridahl; Anders Hansson; et al. (Ambio, 2024)
Drawing on collective experience from ten collaborative research projects focused on the Global South, we identify three major challenges that impede the translation of research on sustainability and resilience into better-informed choices by individuals and policy-makers that in turn can support transformation to a sustainable future. The three challenges comprise: (i) converting knowledge produced during research projects into successful knowledge application; (ii) scaling up knowledge in time when research projects are short-term and potential impacts are long-term; and (iii) scaling up knowledge across space, from local research sites to larger-scale or even global impact. Some potential pathways for funding agencies to overcome these challenges include providing targeted prolonged funding for dissemination and outreach, and facilitating collaboration and coordination across different sites, research teams, and partner organizations. By systematically documenting these challenges, we hope to pave the way for further innovations in the research cycle.

Model Predictive Control in buildings with thermal and visual comfort constraints - Mohammad Khosravi; Benjamin Huber; Antoon Decoussemaeker; Philipp Heer; Roy S. Smith (Energy and Buildings, 2024)

Recommendations for Method Development and Validation of qPCR and dPCR Assays in Support of Cell and Gene Therapy Drug Development - Amanda Hays; Mark Wissel; Kelly Colletti; Russell Soon; Mitra Azadeh; Justin Smith; Rajitha Doddareddy; Melanie Chalfant; Wendy Adamowicz; Swarna Suba Ramaswamy; Sanjay L. Dholakiya; Sebastian Guelman; et al. (The AAPS Journal, 2024)
The emerging use of qPCR and dPCR in regulated bioanalysis and absence of regulatory guidance on assay validations for these platforms has resulted in discussions on lack of harmonization on assay design and appropriate acceptance criteria for these assays. Both qPCR and dPCR are extensively used to answer bioanalytical questions for novel modalities such as cell and gene therapies. Following cross-industry conversations on the lack of information and guidelines for these assays, an American Association of Pharmaceutical Scientists working group was formed to address these gaps by bringing together 37 industry experts from 24 organizations to discuss best practices to gain a better understanding in the industry and facilitate filings to health authorities. Herein, this team provides considerations on assay design, development, and validation testing for PCR assays that are used in cell and gene therapies including (1) biodistribution; (2) transgene expression; (3) viral shedding; (4) and persistence or cellular kinetics of cell therapies. Graphical Abstract

Assessment of no-observed-effect-levels for DNA adducts formation by genotoxic carcinogens in fetal turkey livers - Tetyana Kobets; Christina Hickey; George Johnson; Jian-Dong Duan; Sylvain Etter; Benjamin Smith; Gary M. Williams (Toxicology, 2024)

A class of their own? Water-soluble polymer pollution impacting a freshwater host-pathogen system - Charlotte Robison-Smith; Numair Masud; Eve C. Tarring; Benjamin D. Ward; Jo Cable (Science of The Total Environment, 2024)

Nutrient composition of milk and plant-based milk alternatives: A cross-sectional study of products sold in Australia and Singapore - Paige G. Brooker; Kim Anastasiou; Benjamin P.C. Smith; Rebecca Tan; Xenia Cleanthous; Malcolm D. Riley (Food Research International, 2023)

Synchronising rock clocks of Mars' history: Resolving the shergottite 40Ar/39Ar age paradox - Benjamin E. Cohen; Darren F. Mark; William S. Cassata; Lara M. Kalnins; Martin R. Lee; Caroline L. Smith; David L. Shuster (Earth and Planetary Science Letters, 2023)

Consumption of plant-based meat alternatives by regular consumers and their motivations to sustain long-term intake. - Siti Amelia Juraimi; Florence Sheen; Benjamin Smith; Joseph Simons; Jennifer Gatzemeier; Rochelle Embling; Aimee E. Pink (Appetite, 2023)

Improving photosynthetic efficiency toward food security: Strategies, advances, and perspectives - Edward N. Smith; Marvin van Aalst; Tiina Tosens; Ülo Niinemets; Benjamin Stich; Tomas Morosinotto; Alessandro Alboresi; Tobias J. Erb; Paul A. Gómez-Coronado; Dimitri Tolleter; Giovanni Finazzi; Gilles Curien; et al. (Molecular Plant, 2023)

Bullous keratopathy in a dwarf rabbit (Oryctolagus cuniculus domesticus) - William Irving; Cameron Whittaker; Kelly Caruso; Benjamin Reynolds; Paul McCarthy; Jeff Smith (Journal of Exotic Pet Medicine, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Closing the gap between science and management of cold‐water refuges in rivers and streams - Francine H. Mejia; Valerie Ouellet; Martin A. Briggs; Stephanie M. Carlson; Roser Casas‐Mulet; Mollie Chapman; Mathias J. Collins; Stephen J. Dugdale; Joseph L. Ebersole; Danielle M. Frechette; Aimee H. Fullerton; Carole‐Anne Gillis; et al. (Global Change Biology, 2023)
Human activities and climate change threaten coldwater organisms in freshwater ecosystems by causing rivers and streams to warm, increasing the intensity and frequency of warm temperature events, and reducing thermal heterogeneity. Cold‐water refuges are discrete patches of relatively cool water that are used by coldwater organisms for thermal relief and short‐term survival. Globally, cohesive management approaches are needed that consider interlinked physical, biological, and social factors of cold‐water refuges. We review current understanding of cold‐water refuges, identify gaps between science and management, and evaluate policies aimed at protecting thermally sensitive species. Existing policies include designating cold‐water habitats, restricting fishing during warm periods, and implementing threshold temperature standards or guidelines. However, these policies are rare and uncoordinated across spatial scales and often do not consider input from Indigenous peoples. We propose that cold‐water refuges be managed as distinct operational landscape units, which provide a social and ecological context that is relevant at the watershed scale. These operational landscape units provide the foundation for an integrated framework that links science and management by (1) mapping and characterizing cold‐water refuges to prioritize management and conservation actions, (2) leveraging existing and new policies, (3) improving coordination across jurisdictions, and (4) implementing adaptive management practices across scales. Our findings show that while there are many opportunities for scientific advancement, the current state of the sciences is sufficient to inform policy and management. Our proposed framework provides a path forward for managing and protecting cold‐water refuges using existing and new policies to protect coldwater organisms in the face of global change.

Honey bee drones are synchronously hyperactive inside the nest - Louisa C. Neubauer; Jacob D. Davidson; Benjamin Wild; David M. Dormagen; Tim Landgraf; Iain D. Couzin; Michael L. Smith (Animal Behaviour, 2023)

Multi-site, multi-pollutant atmospheric data analysis using Riemannian geometry - Alexander Smith; Jinxi Hua; Benjamin de Foy; James J. Schauer; Victor M. Zavala (Science of The Total Environment, 2023)

Fungal symbiont community and absence of detectable mycangia in invasive Euplatypus ambrosia beetles - Andre Rodrigues; Andrew J. Johnson; Ross A. Joseph; You Li; Nemat O. Keyhani; Edward L. Stanley; Benjamin Weiss; Martin Kaltenpoth; Matthew E. Smith; Jiri Hulcr (Symbiosis, 2023)

Accidental cultivation of the European truffle Tuber brumale in North American truffle orchards - Benjamin Lemmond; Alassane Sow; Gregory Bonito; Matthew E. Smith (Mycorrhiza, 2023)

Inclusive innovation in just transitions: The case of smart local energy systems in the UK - Adrian Smith; Gerardo A. Torres Contreras; Marie-Claire Brisbois; Max Lacey-Barnacle; Benjamin K. Sovacool (Environmental Innovation and Societal Transitions, 2023)

Inferring inter-colony movement within metapopulations of yellow-footed rock-wallabies using estimates of kinship - Deane A. Smith; Mark R. Lethbridge; Benjamin L. Allen; Rose L. Andrew (Conservation Genetics, 2023)
Understanding the exchange of individuals between wildlife populations, particularly those with naturally fragmented habitats, is important for the effective management of these species. This is of particular consequence when the species is of conservation concern, and isolated populations may be lost due to pressures from predation or competition, or catastrophic events such as wildfire. Here we demonstrate the use kinship and population structure analysis to show potential recent movement between colonies in metapopulations of yellow-footed rock-wallaby ( Petrogale xanthopus Gray 1854) at two sites in the Grey Range of Queensland, and at four sites in the Gawler Ranges of South Australia. These colonies are also compared to a single colony from the Flinders Ranges, a connected landscape of rock-wallaby habitat. Using reduced representation next-generation sequencing, we acquired and filtered a set of ~ 17,000 single-nucleotide polymorphisms to examine population genetic variation, structure and relationships within populations, and also identify putative migrants. Initial STRUCTURE analysis re-confirmed each population should be considered separately. Tests of population genetic variation identify several colonies appearing to be experiencing genetic erosion, also with low calculated effective population sizes (N e = 4.5–36.6). Pairwise comparisons of individual relatedness (relatedness coeffiecients; r ) implied several contemporary movement events between colonies within both the Gawler and Grey Ranges ( r > 0.125), which was then affirmed with tests for putative first generation migrants. These results are of particular note in South Australia, where threat abatement (management of key predators and competitors) may facilitate dispersion. Additionally, in Queensland, colonies are separated by anthropogenic barriers: predator exclusion fencing designed to exclude dingoes ( Canis familiaris ) from grazing land, which may hinder dispersal. This work highlights the usefulness of population genetics to inform management outcomes in wildlife, in this case, highlighting the need for threatened species management at the landscape level.

Consumer habits and practices for cosmetics and personal care products in Singapore: An online survey - Siti Amelia Juraimi; John O’Brien; John Hirsh; Adam Tan; Joshua Teo; Alain Khaiat; Kim Long Yeo; Benjamin P.C. Smith (Food and Chemical Toxicology, 2023)

Statistical analysis of preclinical inter-species concordance of histopathological findings in the eTOX database - Peter S.R. Wright; Katharine A. Briggs; Robert Thomas; Graham F. Smith; Gareth Maglennon; Paulius Mikulskis; Melissa Chapman; Nigel Greene; Benjamin U. Phillips; Andreas Bender (Regulatory Toxicology and Pharmacology, 2023)

Retrospective analysis of the potential use of virtual control groups in preclinical toxicity assessment using the eTOX database - Peter S.R. Wright; Graham F. Smith; Katharine A. Briggs; Robert Thomas; Gareth Maglennon; Paulius Mikulskis; Melissa Chapman; Nigel Greene; Benjamin U. Phillips; Andreas Bender (Regulatory Toxicology and Pharmacology, 2023)

Advancing Diversity and Inclusivity in Ocean Sciences by Re-Envisioning Overlooked Barriers in Scientific Diving Training - Paul Barber; Jeannie Barber-Choi; Austin Betancourt; Benjamin Cuker; Alexandra Davis; Caitlin Fong; Peggy Fong; Deidre Gibson; Tyler Smith (Oceanography, 2023)
Self-contained underwater breathing apparatus (scuba) is an essential tool in some marine science fields. However, financial costs and racial disparities in swimming participation can be a barrier to entry for many aspiring marine scientists of color. Scientific diving programs could improve access to scientific diving training by offering training as part of their standard undergraduate curriculum and by maintaining a stock of scuba gear for use during courses. Similarly, the American Academy of Underwater Scientists (AAUS) could make training more accessible by re-envisioning components of the swim test and by building water safety skills into AAUS training—​all without compromising safety. Combined, these two actions would expand pathways for students of color to careers in marine science, adding much needed diversity to the field.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Development of reconstructed intestinal micronucleus cytome (RICyt) assay in 3D human gut model for genotoxicity assessment of orally ingested substances - Hui Kheng Lim; Christopher Owen Hughes; Michelle Jing Sin Lim; Jia’En Jasmine Li; Moumita Rakshit; Calvin Yeo; Kern Rei Chng; Angela Li; Joanne Sheot Harn Chan; Kee Woei Ng; David Ian Leavesley; Benjamin Paul Chapman Smith (Archives of Toxicology, 2022)
The micronucleus (MN) assay is widely used as part of a battery of tests applied to evaluate the genotoxic potential of chemicals, including new food additives and novel food ingredients. Micronucleus assays typically utilise homogenous in vitro cell lines which poorly recapitulate the physiology, biochemistry and genomic events in the gut, the site of first contact for ingested materials. Here we have adapted and validated the MN endpoint assay protocol for use with complex 3D reconstructed intestinal microtissues; we have named this new protocol the reconstructed intestine micronucleus cytome (RICyt) assay. Our data suggest the commercial 3D microtissues replicate the physiological, biochemical and genomic responses of native human small intestine to exogenous compounds. Tissues were shown to maintain log-phase proliferation throughout the period of exposure and expressed low background MN. Analysis using the RICyt assay protocol revealed the presence of diverse cell types and nuclear anomalies (cytome) in addition to MN, indicating evidence for comprehensive DNA damage and mode(s) of cell death reported by the assay. The assay correctly identified and discriminated direct-acting clastogen, aneugen and clastogen requiring exogenous metabolic activation, and a non-genotoxic chemical. We are confident that the genotoxic response in the 3D microtissues more closely resembles the native tissues due to the inherent tissue architecture, surface area, barrier effects and tissue matrix interactions. This proof-of-concept study highlights the RICyt MN cytome assay in 3D reconstructed intestinal microtissues is a promising tool for applications in predictive toxicology.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

MYT1L-associated neurodevelopmental disorder: description of 40 new cases and literature review of clinical and molecular aspects - Juliette Coursimault; Anne-Marie Guerrot; Michelle M. Morrow; Catherine Schramm; Francisca Millan Zamora; Anita Shanmugham; Shuxi Liu; Fanggeng Zou; Frédéric Bilan; Gwenaël Le Guyader; Ange-Line Bruel; Anne-Sophie Denommé-Pichon; et al. (Human Genetics, 2022)

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Comparing Prochlorococcus temperature niches in the lab and across ocean basins - Alaina N. Smith; Gwenn M. M. Hennon; Erik R. Zinser; Benjamin C. Calfee; Jeremy W. Chandler; Andrew D. Barton (Limnology and Oceanography, 2021)
Niche theory suggests that the realized niche occupied by an organism in the field is a subset of the fundamental niche space of the organism, absent additional biotic and abiotic factors. Though often assumed, this discrepancy is rarely tested for specific organisms, and could act as a source of error in model predictions of biogeographical shifts resulting from temperature change which assume niche theory constraints. Here, we quantify the difference between fundamental and realized temperature niches for four dominant ecotypes of Prochlorococcus , including eMED4, eMIT9312, eMIT9313, and eNATL2A, and ask whether the realized temperature niches of each ecotype vary across ocean basins. The realized niches for the four ecotypes are, on average, 3.84°C ± 1.18°C colder (mean ± SD across all ocean basins and ecotypes) and 2.15°C ± 1.89°C wider than the lab‐measured fundamental niches. When divided into four ocean regions—North Atlantic, South Atlantic, North Pacific, and South Pacific—we find that the realized temperature niche optimum for a given ecotype compared to the fundamental temperature niche optimum differs across regions by as much as 7.93°C, while the niche width can differ by up to 9.48°C. Colder and wider realized niches may be a result of the metabolic risk associated with living in variable environments when the mean temperature is too close to the optimal temperature for growth or due to physical processes such as dispersal. The strong differences in temperature niches across ocean basins suggest that unresolved genetic diversity within ecotypes, local adaptation, and variable interactive ecological and environmental factors are likely to be important in shaping Prochlorococcus realized temperature niches.

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Pre-clinical atherosclerosis is found at post-mortem, in the brains of men with HIV - Olusola Daramola; Hebah Ali; Chris-Anne Mckenzie; Colin Smith; Laura A. Benjamin; Tom Solomon (Journal of NeuroVirology, 2021)
The aim of this study is to ascertain the burden of pre-clinical atherosclerotic changes in the brains of young adult males with HIV and explore the impact of anti-retroviral therapy (ART). The study design is case-control, cross-sectional. Histological sections from HIV-positive post-mortem brain samples, with no associated opportunistic infection, from the MRC Edinburgh brain bank were evaluated. These were age and sex matched with HIV-negative controls. Immunohistochemical stains were performed to evaluate characteristics of atherosclerosis. The pathological changes were graded blinded to the HIV status and a second histopathologist reassessed 15%. Univariable models were used for statistical analyses; p ≤ 0.05 was considered significant. Nineteen HIV-positive post-mortem cases fulfilled our inclusion criteria. Nineteen HIV-negative controls were selected. We assessed mostly small-medium-sized vessels. For inflammation (CD45), 7 (36%) of the HIV+ had moderate/severe changes compared with none for the HIV− group ( p < 0.001). Moderate/severe increase in smooth muscle remodeling (SMA) was found in 8 (42%) HIV+ and 0 HIV− brains ( p < 0.001). Moderate/severe lipoprotein deposition (LOX-1) was found in 3 (15%) and 0 HIV−brains ( p < 0.001). ART was associated with less inflammation [5 (63%) no ART versus 2 (18%) on ART ( p = 0.028)] but was not associated with reduced lipid deposition or smooth muscle damage. In HIV infection, there are pre-clinical small- to medium-sized vessel atherosclerotic changes and ART may have limited impact on these changes. This could have implications on the increasing burden of cerebrovascular disease in HIV populations and warrants further investigation.

Newly discovered cichlid fish biodiversity threatened by hybridization with non‐native species - Tabitha Blackwell; Antonia G. P. Ford; Adam G. Ciezarek; Stephanie J. Bradbeer; Carlos A. Gracida Juarez; Alan M. Smith; Benjamin P. Ngatunga; Asilatu Shechonge; Rashid Tamatamah; Graham Etherington; Wilfried Haerty; Federica Di Palma; et al. (Molecular Ecology, 2021)
Invasive freshwater fishes are known to readily hybridize with indigenous congeneric species, driving loss of unique and irreplaceable genetic resources. Here we reveal that newly discovered (2013–2016) evolutionarily significant populations of Korogwe tilapia ( Oreochromis korogwe ) from southern Tanzania are threatened by hybridization with the larger invasive Nile tilapia ( Oreochromis niloticus ). We use a combination of morphology, microsatellite allele frequencies and whole genome sequences to show that O. korogwe from southern lakes (Nambawala, Rutamba and Mitupa) are distinct from geographically disjunct populations in northern Tanzania (Zigi River and Mlingano Dam). We also provide genetic evidence of O. korogwe × niloticus hybrids in three southern lakes and demonstrate heterogeneity in the extent of admixture across the genome. Finally, using the least admixed genomic regions we estimate that the northern and southern O. korogwe populations most plausibly diverged ~140,000 years ago, suggesting that the geographical separation of the northern and southern groups is not a result of a recent translocation, and instead these populations represent independent evolutionarily significant units. We conclude that these newly discovered and phenotypically unique cichlid populations are already threatened by hybridization with an invasive species, and propose that these irreplaceable genetic resources would benefit from conservation interventions.

Modeling Self-Thinning Patterns in Loblolly Pine with Provenance and Family Effects - Trevor D Walker; Bronson P Bullock; Benjamin C Smith; Steven E McKeand (Forest Science, 2020)
Size-density trajectories and self-thinning boundary lines were modeled for two diverse provenances of Pinus taeda L. and five open-pollinated families within each provenance. The data used come from a single site with replicated 64-tree block plots measured through age 25 years. The effects of provenance and family were tested using linear and nonlinear mixed-effects self-thinning models. The drought-hardy Lost Pines of Texas provenance displayed a greater predicted carrying capacity (almost 200 more trees per hectare at reference diameter 25.4 cm) and had a more abrupt approach to the self-thinning line than the widely planted Atlantic Coastal Plain provenance. However, the growth rate of the Lost Pines of Texas provenance was considerably slower and stem form was unacceptable for timber production. Families from the Atlantic Coastal Plain differed in their maximum stand density index predictions (from 1,118 to 1,282 trees per hectare at the reference diameter), suggesting there is an opportunity for artificial selection to change maximum stand density index in this breeding population of loblolly pine. A novel method for predicting the self-thinning boundary line using random effects inherent to the experimental design is presented and recommended for repeated measures data. Experimental design considerations for evaluating genetic differences in self-thinning are discussed. Study Implications Genetic improvement of growth rate in forest trees has resulted in large gains in plantation productivity, but the effect on carrying capacity has not been addressed. This study indicated that artificial selection on tolerance to competition in the widely planted Atlantic Coastal Plain provenance of loblolly pine can potentially increase harvest yield without sacrificing growth rate. The drought-hardy Lost Pines of Texas provenance displayed greater carrying capacity but had poor stem form and slow growth. The Lost Pines provenance may be attractive for aboveground carbon sequestration, since it sustained substantially more biomass because of greater maximum stand density and denser wood.

The role of methane in future climate strategies: mitigation potentials and climate impacts - Mathijs Harmsen; Detlef P. van Vuuren; Benjamin Leon Bodirsky; Jean Chateau; Olivier Durand-Lasserve; Laurent Drouet; Oliver Fricko; Shinichiro Fujimori; David E. H. J. Gernaat; Tatsuya Hanaoka; Jérôme Hilaire; Kimon Keramidas; et al. (Climatic Change, 2020)
This study examines model-specific assumptions and projections of methane (CH 4 ) emissions in deep mitigation scenarios generated by integrated assessment models (IAMs). For this, scenarios of nine models are compared in terms of sectoral and regional CH 4 emission reduction strategies, as well as resulting climate impacts. The models’ projected reduction potentials are compared to sector and technology-specific reduction potentials found in literature. Significant cost-effective and non-climate policy related reductions are projected in the reference case (10–36% compared to a “frozen emission factor” scenario in 2100). Still, compared to 2010, CH 4 emissions are expected to rise steadily by 9–72% (up to 412 to 654 Mt CH 4 /year). Ambitious CO 2 reduction measures could by themselves lead to a reduction of CH 4 emissions due to a reduction of fossil fuels (22–48% compared to the reference case in 2100). However, direct CH 4 mitigation is crucial and more effective in bringing down CH 4 (50–74% compared to the reference case). Given the limited reduction potential, agriculture CH 4 emissions are projected to constitute an increasingly larger share of total anthropogenic CH 4 emissions in mitigation scenarios. Enteric fermentation in ruminants is in that respect by far the largest mitigation bottleneck later in the century with a projected 40–78% of total remaining CH 4 emissions in 2100 in a strong (2 °C) climate policy case.

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Enhanced Characterization of Pyrene Binding in Mixed Cyclodextrin Systems via Fluorescence Spectroscopy - Mindy Levine; Benjamin R. Smith (Journal of Fluorescence, 2020)

Modelling past and future peatland carbon dynamics across the pan‐Arctic - Nitin Chaudhary; Sebastian Westermann; Shubhangi Lamba; Narasinha Shurpali; A. Britta K. Sannel; Guy Schurgers; Paul A. Miller; Benjamin Smith (Global Change Biology, 2020)
The majority of northern peatlands were initiated during the Holocene. Owing to their mass imbalance, they have sequestered huge amounts of carbon in terrestrial ecosystems. Although recent syntheses have filled some knowledge gaps, the extent and remoteness of many peatlands pose challenges to developing reliable regional carbon accumulation estimates from observations. In this work, we employed an individual‐ and patch‐based dynamic global vegetation model (LPJ‐GUESS) with peatland and permafrost functionality to quantify long‐term carbon accumulation rates in northern peatlands and to assess the effects of historical and projected future climate change on peatland carbon balance. We combined published datasets of peat basal age to form an up‐to‐date peat inception surface for the pan‐Arctic region which we then used to constrain the model. We divided our analysis into two parts, with a focus both on the carbon accumulation changes detected within the observed peatland boundary and at pan‐Arctic scale under two contrasting warming scenarios (representative concentration pathway—RCP8.5 and RCP2.6). We found that peatlands continue to act as carbon sinks under both warming scenarios, but their sink capacity will be substantially reduced under the high‐warming (RCP8.5) scenario after 2050. Areas where peat production was initially hampered by permafrost and low productivity were found to accumulate more carbon because of the initial warming and moisture‐rich environment due to permafrost thaw, higher precipitation and elevated CO 2 levels. On the other hand, we project that areas which will experience reduced precipitation rates and those without permafrost will lose more carbon in the near future, particularly peatlands located in the European region and between 45 and 55°N latitude. Overall, we found that rapid global warming could reduce the carbon sink capacity of the northern peatlands in the coming decades.

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos - Nicholas M. A. Smith; Boris Yagound; Emily J. Remnant; Charles S. P. Foster; Gabriele Buchmann; Michael H. Allsopp; Clement F. Kent; Amro Zayed; Stephen A. Rose; Kitty Lo; Alyson Ashe; Brock A. Harpur; et al. (Molecular Ecology, 2020)
The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele .

Higher than expected CO 2 fertilization inferred from leaf to global observations - Vanessa Haverd; Benjamin Smith; Josep G. Canadell; Matthias Cuntz; Sara Mikaloff‐Fletcher; Graham Farquhar; William Woodgate; Peter R. Briggs; Cathy M. Trudinger (Global Change Biology, 2020)
Several lines of evidence point to an increase in the activity of the terrestrial biosphere over recent decades, impacting the global net land carbon sink (NLS) and its control on the growth of atmospheric carbon dioxide ( c a ). Global terrestrial gross primary production (GPP)—the rate of carbon fixation by photosynthesis—is estimated to have risen by (31 ± 5)% since 1900, but the relative contributions of different putative drivers to this increase are not well known. Here we identify the rising atmospheric CO 2 concentration as the dominant driver. We reconcile leaf‐level and global atmospheric constraints on trends in modeled biospheric activity to reveal a global CO 2 fertilization effect on photosynthesis of 30% since 1900, or 47% for a doubling of c a above the pre‐industrial level. Our historic value is nearly twice as high as current estimates (17 ± 4)% that do not use the full range of available constraints. Consequently, under a future low‐emission scenario, we project a land carbon sink (174 PgC, 2006–2099) that is 57 PgC larger than if a lower CO 2 fertilization effect comparable with current estimates is assumed. These findings suggest a larger beneficial role of the land carbon sink in modulating future excess anthropogenic CO 2 consistent with the target of the Paris Agreement to stay below 2°C warming, and underscore the importance of preserving terrestrial carbon sinks.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Ocean FAIR Data Services - Toste Tanhua; Sylvie Pouliquen; Jessica Hausman; Kevin O’Brien; Pip Bricher; Taco de Bruin; Justin J. H. Buck; Eugene F. Burger; Thierry Carval; Kenneth S. Casey; Steve Diggs; Alessandra Giorgetti; et al. (Frontiers in Marine Science, 2019)

Population genetic evidence for a unique resource of Nile tilapia in Lake Tanganyika, East Africa - Asilatu Shechonge; Benjamin P. Ngatunga; Rashid Tamatamah; Stephanie J. Bradbeer; Emmanuel Sweke; Alan Smith; George F. Turner; Martin J. Genner (Environmental Biology of Fishes, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Coring of Antarctic Subglacial Sediments - Da Gong; Xiaopeng Fan; Yazhou Li; Bing Li; Nan Zhang; Raphael Gromig; Emma C. Smith; Wolf Dummann; Sophie Berger; Olaf Eisen; Jan Tell; Boris K. Biskaborn; et al. (Journal of Marine Science and Engineering, 2019)
Coring sediments in subglacial aquatic environments offers unique opportunities for research on paleo-environments and paleo-climates because it can provide data from periods even earlier than ice cores, as well as the overlying ice histories, interactions between ice and the water system, life forms in extreme habitats, sedimentology, and stratigraphy. However, retrieving sediment cores from a subglacial environment faces more difficulties than sediment coring in oceans and lakes, resulting in low yields from the most current subglacial sediment coring methods. The coring tools should pass through a hot water-drilled access borehole, then the water column, to reach the sediment layers. The access boreholes are size-limited by the hot water drilling tools and techniques. These holes are drilled through ice up to 3000–4000 m thick, with diameters ranging from 10–60 cm, and with a refreezing closure rate of up to 6 mm/h after being drilled. Several purpose-built streamline corers have been developed to pass through access boreholes and collect the sediment core. The main coring objectives are as follows: (i) To obtain undisturbed water–sediment cores, either singly or as multi-cores and (ii) to obtain long cores with minimal stratigraphic deformation. Subglacial sediment coring methods use similar tools to those used in lake and ocean coring. These methods include the following: Gravity coring, push coring, piston coring, hammer or percussion coring, vibrocoring, and composite methods. Several core length records have been attained by different coring methods, including a 290 cm percussion core from the sub-ice-shelf seafloor, a 400 cm piston core from the sub-ice-stream, and a 170 cm gravity core from a subglacial lake. There are also several undisturbed water–sediment cores that have been obtained by gravity corers or hammer corers. Most current coring tools are deployed by winch and cable facilities on the ice surface. There are three main limitations for obtaining long sediment cores which determines coring tool development, as follows: Hot-water borehole radial size restriction, the sedimentary structure, and the coring techniques. In this paper, we provide a general view on current developments in coring tools, including the working principles, corer characteristics, operational methods, coring site locations, field conditions, coring results, and possible technical improvements. Future prospects in corer design and development are also discussed.

Correction to: Widespread colonisation of Tanzanian catchments by introduced Oreochromis tilapia fishes: the legacy from decades of deliberate introduction - Asilatu Shechonge; Benjamin P. Ngatunga; Stephanie J. Bradbeer; Julia J. Day; Jennifer J. Freer; Antonia G. P. Ford; Jonathan Kihedu; Tabitha Richmond; Semvua Mzighani; Alan M. Smith; Emmanuel A. Sweke; Rashid Tamatamah; et al. (Hydrobiologia, 2019)

Widespread colonisation of Tanzanian catchments by introduced Oreochromis tilapia fishes: the legacy from decades of deliberate introduction - Asilatu Shechonge; Benjamin P. Ngatunga; Stephanie J. Bradbeer; Julia J. Day; Jennifer J. Freer; Antonia G. P. Ford; Jonathan Kihedu; Tabitha Richmond; Semvua Mzighani; Alan M. Smith; Emmanuel A. Sweke; Rashid Tamatamah; et al. (Hydrobiologia, 2019)

Limited hybridization between introduced and Critically Endangered indigenous tilapia fishes in northern Tanzania - Stephanie J. Bradbeer; Jack Harrington; Henry Watson; Abrahim Warraich; Asilatu Shechonge; Alan Smith; Rashid Tamatamah; Benjamin P. Ngatunga; George F. Turner; Martin J. Genner (Hydrobiologia, 2019)

Developing an Integrated Ocean Observing System for New Zealand - Joanne O’Callaghan; Craig Stevens; Moninya Roughan; Chris Cornelisen; Philip Sutton; Sally Garrett; Giacomo Giorli; Robert O. Smith; Kim I. Currie; Sutara H. Suanda; Michael Williams; Melissa Bowen; et al. (Frontiers in Marine Science, 2019)

Implications of range overlap in the commercially important pan-tropical sea urchin genus Tripneustes (Echinoidea: Toxopneustidae) - Omri Bronstein; Andreas Kroh; Ashley D. Miskelly; Stephen D. A. Smith; Symon A. Dworjanyn; Benjamin Mos; Maria Byrne (Marine Biology, 2019)

Integrating real-time subsurface hydrologic monitoring with empirical rainfall thresholds to improve landslide early warning - Benjamin B. Mirus; Rachel E. Becker; Rex L. Baum; Joel B. Smith (Landslides, 2018)

Biotic and Abiotic Drivers of Peatland Growth and Microtopography: A Model Demonstration - Nitin Chaudhary; Paul A. Miller; Benjamin Smith (Ecosystems, 2018)

Altered white matter development in children born very preterm - Julia M. Young; Marlee M. Vandewouw; Benjamin R. Morgan; Mary Lou Smith; John G. Sled; Margot J. Taylor (Brain Structure and Function, 2018)

Thermal refugia against coral bleaching throughout the northern Red Sea - Eslam O. Osman; David J. Smith; Maren Ziegler; Benjamin Kürten; Constanze Conrad; Khaled M. El‐Haddad; Christian R. Voolstra; David J. Suggett (Global Change Biology, 2018)
Tropical reefs have been impacted by thermal anomalies caused by global warming that induced coral bleaching and mortality events globally. However, there have only been very few recordings of bleaching within the Red Sea despite covering a latitudinal range of 15° and consequently it has been considered a region that is less sensitive to thermal anomalies. We therefore examined historical patterns of sea surface temperature ( SST ) and associated anomalies (1982–2012) and compared warming trends with a unique compilation of corresponding coral bleaching records from throughout the region. These data indicated that the northern Red Sea has not experienced mass bleaching despite intensive Degree Heating Weeks ( DHW ) of >15°C‐weeks. Severe bleaching was restricted to the central and southern Red Sea where DHW s have been more frequent, but far less intense (DHWs 8°C‐weeks), and bleaching was restricted to the central and southern Red Sea despite the lower thermal stress ( DHW s

Vegetation demographics in Earth System Models: A review of progress and priorities - Rosie A. Fisher; Charles D. Koven; William R. L. Anderegg; Bradley O. Christoffersen; Michael C. Dietze; Caroline E. Farrior; Jennifer A. Holm; George C. Hurtt; Ryan G. Knox; Peter J. Lawrence; Jeremy W. Lichstein; Marcos Longo; et al. (Global Change Biology, 2018)
Numerous current efforts seek to improve the representation of ecosystem ecology and vegetation demographic processes within Earth System Models ( ESM s). These developments are widely viewed as an important step in developing greater realism in predictions of future ecosystem states and fluxes. Increased realism, however, leads to increased model complexity, with new features raising a suite of ecological questions that require empirical constraints. Here, we review the developments that permit the representation of plant demographics in ESM s, and identify issues raised by these developments that highlight important gaps in ecological understanding. These issues inevitably translate into uncertainty in model projections but also allow models to be applied to new processes and questions concerning the dynamics of real‐world ecosystems. We argue that stronger and more innovative connections to data, across the range of scales considered, are required to address these gaps in understanding. The development of first‐generation land surface models as a unifying framework for ecophysiological understanding stimulated much research into plant physiological traits and gas exchange. Constraining predictions at ecologically relevant spatial and temporal scales will require a similar investment of effort and intensified inter‐disciplinary communication.

Application of Landsat 8 for Monitoring Impacts of Wastewater Discharge on Coastal Water Quality - Rebecca C. Trinh; Cédric G. Fichot; Michelle M. Gierach; Benjamin Holt; Nabin K. Malakar; Glynn Hulley; Jayme Smith (Frontiers in Marine Science, 2017)

Offshore Aquaculture: I Know It When I See It - Halley E. Froehlich; Alexandra Smith; Rebecca R. Gentry; Benjamin S. Halpern (Frontiers in Marine Science, 2017)

Perceptions matter: household adaptive capacity and capability in two Australian coastal communities - Carmen E. Elrick-Barr; Dana C. Thomsen; Benjamin L. Preston; Timothy F. Smith (Regional Environmental Change, 2017)

Carbon cycle responses of semi‐arid ecosystems to positive asymmetry in rainfall - Vanessa Haverd; Anders Ahlström; Benjamin Smith; Josep G. Canadell (Global Change Biology, 2017)
Recent evidence shows that warm semi‐arid ecosystems are playing a disproportionate role in the interannual variability and greening trend of the global carbon cycle given their mean lower productivity when compared with other biomes (Ahlström et al . 2015 Science , 348, 895). Using multiple observations (land‐atmosphere fluxes, biomass, streamflow and remotely sensed vegetation cover) and two state‐of‐the‐art biospheric models, we show that climate variability and extremes lead to positive or negative responses in the biosphere, depending on vegetation type. We find Australia to be a global hot spot for variability, with semi‐arid ecosystems in that country exhibiting increased carbon uptake due to both asymmetry in the interannual distribution of rainfall (extrinsic forcing), and asymmetry in the response of gross primary production ( GPP ) to rainfall change (intrinsic response). The latter is attributable to the pulse‐response behaviour of the drought‐adapted biota of these systems, a response that is estimated to be as much as half of that from the CO 2 fertilization effect during 1990–2013. Mesic ecosystems, lacking drought‐adapted species, did not show an intrinsic asymmetric response. Our findings suggest that a future more variable climate will induce large but contrasting ecosystem responses, differing among biomes globally, independent of changes in mean precipitation alone. The most significant changes are occurring in the extensive arid and semi‐arid regions, and we suggest that the reported increased carbon uptake in response to asymmetric responses might be contributing to the observed greening trends there.

Using models to guide field experiments: a priori predictions for the CO 2 response of a nutrient‐ and water‐limited native Eucalypt woodland - Belinda E. Medlyn; Martin G. De Kauwe; Sönke Zaehle; Anthony P. Walker; Remko A. Duursma; Kristina Luus; Mikhail Mishurov; Bernard Pak; Benjamin Smith; Ying‐Ping Wang; Xiaojuan Yang; Kristine Y. Crous; et al. (Global Change Biology, 2016)
The response of terrestrial ecosystems to rising atmospheric CO 2 concentration (C a ), particularly under nutrient‐limited conditions, is a major uncertainty in Earth System models. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment, recently established in a nutrient‐ and water‐limited woodland presents a unique opportunity to address this uncertainty, but can best do so if key model uncertainties have been identified in advance. We applied seven vegetation models, which have previously been comprehensively assessed against earlier forest FACE experiments, to simulate a priori possible outcomes from Euc FACE . Our goals were to provide quantitative projections against which to evaluate data as they are collected, and to identify key measurements that should be made in the experiment to allow discrimination among alternative model assumptions in a postexperiment model intercomparison. Simulated responses of annual net primary productivity ( NPP ) to elevated C a ranged from 0.5 to 25% across models. The simulated reduction of NPP during a low‐rainfall year also varied widely, from 24 to 70%. Key processes where assumptions caused disagreement among models included nutrient limitations to growth; feedbacks to nutrient uptake; autotrophic respiration; and the impact of low soil moisture availability on plant processes. Knowledge of the causes of variation among models is now guiding data collection in the experiment, with the expectation that the experimental data can optimally inform future model improvements.

Dryland vegetation response to wet episode, not inherent shift in sensitivity to rainfall, behind Australia's role in 2011 global carbon sink anomaly - Vanessa Haverd; Benjamin Smith; Cathy Trudinger (Global Change Biology, 2016)

Immunology and cartilage regeneration - Benjamin Smith; Ian R. Sigal; Daniel A. Grande (Immunologic Research, 2015)

Lowhead dams and the downstream dispersal of zebra mussels - Benjamin R. Smith; David R. Edds; Jason M. Goeckler (Hydrobiologia, 2015)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

High-resolution rainfall variability simulated by the WRF RCM: application to eastern France - Romain Marteau; Yves Richard; Benjamin Pohl; Carmela Chateau Smith; Thierry Castel (Climate Dynamics, 2015)

Forest management facing climate change - an ecosystem model analysis of adaptation strategies - Anna Maria Jönsson; Fredrik Lagergren; Benjamin Smith (Mitigation and Adaptation Strategies for Global Change, 2015)

Amphibian Community Responses to Playa Restoration in the Rainwater Basin - Benjamin J. Beas; Loren M. Smith (Wetlands, 2014)

Validating DICOM Transcoding with an Open Multi-Format Resource - Benjamin C. Yvernault; Charles D. Theobald; Jolinda C. Smith; Victoria Villalta; David H. Zald; Bennett A. Landman (Neuroinformatics, 2014)

The non-native turf-forming alga Caulacanthus ustulatus displaces space-occupants but increases diversity - Jayson R. Smith; Sean C. Vogt; Faye Creedon; Benjamin J. Lucas; Douglas J. Eernisse (Biological Invasions, 2014)

Influence of exercise intensity on respiratory muscle fatigue and brachial artery blood flow during cycling exercise - Joshua R. Smith; Carl J. Ade; Ryan M. Broxterman; Benjamin C. Skutnik; Thomas J. Barstow; Brett J. Wong; Craig A. Harms (European Journal of Applied Physiology, 2014)

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Novel tools for characterising inter and intra chromosomal rearrangements in avian microchromosomes - Pamela E Lithgow; Rebecca O’Connor; Deborah Smith; Gothami Fonseka; Abdullah Al Mutery; Claudia Rathje; Richard Frodsham; Patricia O’Brien; Fumio Kasai; Malcolm A. Ferguson-Smith; Benjamin M. Skinner; Darren K. Griffin (Chromosome Research, 2014)

Global patterns of apparent copy number variation in birds revealed by cross-species comparative genomic hybridization - Benjamin M. Skinner; Abdullah Al Mutery; Deborah Smith; Martin Völker; Nilofour Hojjat; Sannaa Raja; Steven Trim; Peter Houde; William J. Boecklen; Darren K. Griffin (Chromosome Research, 2014)

The corallivorous flatworm Amakusaplana acroporae: an invasive species threat to coral reefs? - Benjamin C. C. Hume; Cecilia D’Angelo; Anna Cunnington; Edward G. Smith; Jörg Wiedenmann (Coral Reefs, 2014)

Quantitative exploration of the contribution of settlement, growth, dispersal and grazing to the accumulation of natural marine biofilms on antifouling and fouling-release coatings - Benjamin A.S. Van Mooy; Laura R. Hmelo; Helen F. Fredricks; Justin E. Ossolinski; Byron E. Pedler; Daniel J. Bogorff; Peter J.S. Smith (Biofouling, 2014)

Biogeochemical Control of the Coupled CO2–O2 System of the Baltic Sea: A Review of the Results of Baltic-C - Anders Omstedt; Christoph Humborg; Janusz Pempkowiak; Matti Perttilä; Anna Rutgersson; Bernd Schneider; Benjamin Smith (Ambio, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Genome-wide copy number variation analysis of a Branchio-oto-renal syndrome cohort identifies a recombination hotspot and implicates new candidate genes - Patrick D. Brophy; Fatemeh Alasti; Benjamin W. Darbro; Jason Clarke; Carla Nishimura; Bryan Cobb; Richard J. Smith; J. Robert Manak (Human Genetics, 2013)

The transmitting tissue of Nicotiana tabacum is not essential to pollen tube growth, and its ablation can reverse prezygotic interspecific barriers - Alan G. Smith; Carrie A. Eberle; Nicole G. Moss; Neil O. Anderson; Benjamin M. Clasen; Adrian D. Hegeman (Plant Reproduction, 2013)

Soil microbial biomass and the fate of phosphorus during long-term ecosystem development - Benjamin L. Turner; Hans Lambers; Leo M. Condron; Michael D. Cramer; Jonathan R. Leake; Alan E. Richardson; Sally E. Smith (Plant and Soil, 2013)

Heat waves in the United States: definitions, patterns and trends - Tiffany T. Smith; Benjamin F. Zaitchik; Julia M. Gohlke (Climatic Change, 2013)

Forest water use and water use efficiency at elevated CO 2 : a model‐data intercomparison at two contrasting temperate forest FACE sites - Martin G. De Kauwe; Belinda E. Medlyn; Sönke Zaehle; Anthony P. Walker; Michael C. Dietze; Thomas Hickler; Atul K. Jain; Yiqi Luo; William J. Parton; I. Colin Prentice; Benjamin Smith; Peter E. Thornton; et al. (Global Change Biology, 2013)
Predicted responses of transpiration to elevated atmospheric CO 2 concentration ( eCO 2 ) are highly variable amongst process‐based models. To better understand and constrain this variability amongst models, we conducted an intercomparison of 11 ecosystem models applied to data from two forest free‐air CO 2 enrichment ( FACE ) experiments at Duke University and Oak Ridge National Laboratory. We analysed model structures to identify the key underlying assumptions causing differences in model predictions of transpiration and canopy water use efficiency. We then compared the models against data to identify model assumptions that are incorrect or are large sources of uncertainty. We found that model‐to‐model and model‐to‐observations differences resulted from four key sets of assumptions, namely (i) the nature of the stomatal response to elevated CO 2 (coupling between photosynthesis and stomata was supported by the data); (ii) the roles of the leaf and atmospheric boundary layer (models which assumed multiple conductance terms in series predicted more decoupled fluxes than observed at the broadleaf site); (iii) the treatment of canopy interception (large intermodel variability, 2–15%); and (iv) the impact of soil moisture stress (process uncertainty in how models limit carbon and water fluxes during moisture stress). Overall, model predictions of the CO 2 effect on WUE were reasonable (intermodel μ = approximately 28% ± 10%) compared to the observations (μ = approximately 30% ± 13%) at the well‐coupled coniferous site (Duke), but poor (intermodel μ = approximately 24% ± 6%; observations μ = approximately 38% ± 7%) at the broadleaf site (Oak Ridge). The study yields a framework for analysing and interpreting model predictions of transpiration responses to eCO 2 , and highlights key improvements to these types of models.

Haplotype diversity and population structure in cultivated and wild barley evaluated for Fusarium head blight responses - Yadong Huang; Benjamin P. Millett; Karen A. Beaubien; Stephanie K. Dahl; Brian J. Steffenson; Kevin P. Smith; Gary J. Muehlbauer (Theoretical and Applied Genetics, 2013)

Evaluation of a digital microfluidic real-time PCR platform to detect DNA of Candida albicans in blood - W. A. Schell; J. L. Benton; P. B. Smith; M. Poore; J. L. Rouse; D. J. Boles; M. D. Johnson; B. D. Alexander; V. K. Pamula; A. E. Eckhardt; M. G. Pollack; D. K. Benjamin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

The potential transient dynamics of forests in New England under historical and projected future climate change - Guoping Tang; Brian Beckage; Benjamin Smith (Climatic Change, 2012)

Modelling Tundra Vegetation Response to Recent Arctic Warming - Paul A. Miller; Benjamin Smith (Ambio, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

High site fidelity and low site connectivity in temperate salt marsh fish populations: a stable isotope approach - Benjamin C. Green; David J. Smith; Jonathan Grey; Graham J. C. Underwood (Oecologia, 2012)

Projecting the future distribution of European potential natural vegetation zones with a generalized, tree species‐based dynamic vegetation model - Thomas Hickler; Katrin Vohland; Jane Feehan; Paul A. Miller; Benjamin Smith; Luis Costa; Thomas Giesecke; Stefan Fronzek; Timothy R. Carter; Wolfgang Cramer; Ingolf Kühn; Martin T. Sykes (Global Ecology and Biogeography, 2012)
Aim To assess the extent to which climate change might cause changes in potential natural vegetation (PNV) across Europe. Location Europe. Method We parameterized a generalized dynamic vegetation model (LPJ‐GUESS) for the most common European tree species, and, for the first time, modelled large‐scale vegetation dynamics using a process‐based model explicitly representing tree species, age cohorts, gap dynamics and biogeochemical cycles in a single framework. For projections, the model was driven with climate scenario data from two atmosphere–ocean general circulation models (AOGCMs), downscaled to 10 × 10′ spatial resolution ( c . 18.5 × 12 km at 50° N). Results At a general level, modelled present‐day PNV corresponded better with an expert reconstruction of the PNV than most earlier plant functional type (PFT)‐based simulations, but at a finer scale the model and the expert map showed substantial discrepancies in some areas. Simulations until 2085 showed considerable successional shifts in vegetation types in most areas: 31–42% of the total area of Europe was projected to be covered by a different vegetation type by the year 2085. In the long term, equilibrium changes are substantially larger: simulations with one climate scenario suggest that 76–80% of the European land surface could exist within another PNV if climate was stabilized by the end of the century and vegetation had unlimited time to achieve equilibrium with the new climate. ‘Hotspots’ of change include arctic and alpine ecosystems, where trees replace tundra in the model, and the transition zone between temperate broad‐leaved and boreal conifer forest. In southern Europe, the model projected widespread shifts from forest to shrublands as a result of drought. Main conclusions The model presents a considerable advance in modelling dynamic changes in natural vegetation across Europe. Climate change might cause substantial changes in PNV across Europe, which should be considered in the management of reserves and forestry.

Adapting to climate change through local municipal planning: barriers and challenges - Thomas G. Measham; Benjamin L. Preston; Timothy F. Smith; Cassandra Brooke; Russell Gorddard; Geoff Withycombe; Craig Morrison (Mitigation and Adaptation Strategies for Global Change, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Genome of alkaliphilic Bacillus pseudofirmus OF4 reveals adaptations that support the ability to grow in an external pH range from 7.5 to 11.4 - Benjamin Janto; Azad Ahmed; Masahiro Ito; Jun Liu; David B. Hicks; Sarah Pagni; Oliver J. Fackelmayer; Terry‐Ann Smith; Joshua Earl; Liam D.H. Elbourne; Karl Hassan; Ian T. Paulsen; et al. (Environmental Microbiology, 2011)
Summary Bacillus pseudofirmus OF4 is an extreme but facultative alkaliphile that grows non‐fermentatively in a pH range from 7.5 to above 11.4 and can withstand large sudden increases in external pH. It is a model organism for studies of bioenergetics at high pH, at which energy demands are higher than at neutral pH because both cytoplasmic pH homeostasis and ATP synthesis require more energy. The alkaliphile also tolerates a cytoplasmic pH > 9.0 at external pH values at which the pH homeostasis capacity is exceeded, and manages other stresses that are exacerbated at alkaline pH, e.g. sodium, oxidative and cell wall stresses. The genome of B. pseudofirmus OF4 includes two plasmids that are lost from some mutants without viability loss. The plasmids may provide a reservoir of mobile elements that promote adaptive chromosomal rearrangements under particular environmental conditions. The genome also reveals a more acidic pI profile for proteins exposed on the outer surface than found in neutralophiles. A large array of transporters and regulatory genes are predicted to protect the alkaliphile from its overlapping stresses. In addition, unanticipated metabolic versatility was observed, which could ensure requisite energy for alkaliphily under diverse conditions.

Effect of resistance training during hemodialysis on circulating cytokines: a randomized controlled trial - Birinder Singh Bobby Cheema; Haifa Abas; Benjamin C. F. Smith; Anthony J. O’Sullivan; Maria Chan; Aditi Patwardhan; John Kelly; Adrian Gillin; Glen Pang; Brad Lloyd; Klaus Berger; Bernhard T. Baune; et al. (European Journal of Applied Physiology, 2011)

Quantitative trait loci conferring resistance to Fusarium head blight in barley respond differentially to Fusarium graminearum infection - Haiyan Jia; Benjamin P. Millett; Seungho Cho; Hatice Bilgic; Wayne W. Xu; Kevin P. Smith; Gary J. Muehlbauer (Functional & Integrative Genomics, 2011)

Analysis of Bead Sizes for MR Capsules Labeled for Sprinkle - Laxma R. Nagavelli; Robert A. Lionberger; Vilayat A. Sayeed; Lawrence Yu; James Allgire; Anjanette Smith; Anna Wokovich; Benjamin J. Westenberger; Lucinda Buhse (AAPS PharmSciTech, 2010)

Implications of future climate and atmospheric CO 2 content for regional biogeochemistry, biogeography and ecosystem services across East Africa - RUTH M. DOHERTY; STEPHEN SITCH; BENJAMIN SMITH; SIMON L. LEWIS; PHILIP K. THORNTON (Global Change Biology, 2010)
We model future changes in land biogeochemistry and biogeography across East Africa. East Africa is one of few tropical regions where general circulation model (GCM) future climate projections exhibit a robust response of strong future warming and general annual‐mean rainfall increases. Eighteen future climate projections from nine GCMs participating in the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment were used as input to the LPJ dynamic global vegetation model (DGVM), which predicted vegetation patterns and carbon storage in agreement with satellite observations and forest inventory data under the present‐day climate. All simulations showed future increases in tropical woody vegetation over the region at the expense of grasslands. Regional increases in net primary productivity (NPP) (18–36%) and total carbon storage (3–13%) by 2080–2099 compared with the present‐day were common to all simulations. Despite decreases in soil carbon after 2050, seven out of nine simulations continued to show an annual net land carbon sink in the final decades of the 21st century because vegetation biomass continued to increase. The seasonal cycles of rainfall and soil moisture show future increases in wet season rainfall across the GCMs with generally little change in dry season rainfall. Based on the simulated present‐day climate and its future trends, the GCMs can be grouped into four broad categories. Overall, our model results suggest that East Africa, a populous and economically poor region, is likely to experience some ecosystem service benefits through increased precipitation, river runoff and fresh water availability. Resulting enhancements in NPP may lead to improved crop yields in some areas. Our results stand in partial contradiction to other studies that suggest possible negative consequences for agriculture, biodiversity and other ecosystem services caused by temperature increases.

Dietary exposure to titanium dioxide nanoparticles in rainbow trout, (Oncorhynchus mykiss): no effect on growth, but subtle biochemical disturbances in the brain - Christopher S. Ramsden; Timothy J. Smith; Benjamin J. Shaw; Richard D. Handy (Ecotoxicology, 2009)

The binding of analogs of porphyrins and chlorins with elongated side chains to albumin - Shimshon Ben Dror; Irena Bronshtein; Hana Weitman; Kevin M. Smith; William G. O’Neal; Peter A. Jacobi; Benjamin Ehrenberg (European Biophysics Journal, 2009)

Reservoir Based Fentanyl Transdermal Drug Delivery Systems: Effect of Patch Age on Drug Release and Skin Permeation - Suneela Prodduturi; Glen J. Smith; Anna M. Wokovich; William H. Doub; Benjamin J. Westenberger; Lucinda Buhse (Pharmaceutical Research, 2009)

Perchlorate Distribution, Excretion, and Depuration in Prairie Voles and Deer Mice - Qiuqiong Cheng; Fujun Liu; Philip N. Smith; W. Andrew Jackson; Scott T. McMurry; Michael J. Hooper; Ernest E. Smith; Benjamin C. Blount; Liza Valentin-Blasini; Todd A. Anderson (Water, Air, & Soil Pollution, 2008)

CO 2 fertilization in temperate FACE experiments not representative of boreal and tropical forests - THOMAS HICKLER; BENJAMIN SMITH; I. COLIN PRENTICE; KRISTINA MJÖFORS; PAUL MILLER; ALMUT ARNETH; MARTIN T. SYKES (Global Change Biology, 2008)
Results from free‐air CO 2 enrichment (FACE) experiments in temperate climates indicate that the response of forest net primary productivity (NPP) to elevated CO 2 might be highly conserved across a broad range of productivities. In this study, we show that the LPJ‐GUESS dynamic vegetation model reproduces the magnitude of the NPP enhancement at temperate forest FACE experiments. A global application of the model suggests that the response found in the experiments might also be representative of the average response of forests globally. However, the predicted NPP enhancement in tropical forests is more than twice as high as in boreal forests, suggesting that currently available FACE results are not applicable to these ecosystems. The modeled geographic pattern is to a large extent driven by the temperature dependence of the relative affinities of the primary assimilation enzyme (Rubisco) for CO 2 and O 2 .

A cross‐system synthesis of consumer and nutrient resource control on producer biomass - Daniel S. Gruner; Jennifer E. Smith; Eric W. Seabloom; Stuart A. Sandin; Jacqueline T. Ngai; Helmut Hillebrand; W. Stanley Harpole; James J. Elser; Elsa E. Cleland; Matthew E. S. Bracken; Elizabeth T. Borer; Benjamin M. Bolker (Ecology Letters, 2008)
Nutrient availability and herbivory control the biomass of primary producer communities to varying degrees across ecosystems. Ecological theory, individual experiments in many different systems, and system‐specific quantitative reviews have suggested that (i) bottom–up control is pervasive but top–down control is more influential in aquatic habitats relative to terrestrial systems and (ii) bottom–up and top–down forces are interdependent, with statistical interactions that synergize or dampen relative influences on producer biomass. We used simple dynamic models to review ecological mechanisms that generate independent vs. interactive responses of community‐level biomass. We calibrated these mechanistic predictions with the metrics of factorial meta‐analysis and tested their prevalence across freshwater, marine and terrestrial ecosystems with a comprehensive meta‐analysis of 191 factorial manipulations of herbivores and nutrients. Our analysis showed that producer community biomass increased with fertilization across all systems, although increases were greatest in freshwater habitats. Herbivore removal generally increased producer biomass in both freshwater and marine systems, but effects were inconsistent on land. With the exception of marine temperate rocky reef systems that showed positive synergism of nutrient enrichment and herbivore removal, experimental studies showed limited support for statistical interactions between nutrient and herbivory treatments on producer biomass. Top–down control of herbivores, compensatory behaviour of multiple herbivore guilds, spatial and temporal heterogeneity of interactions, and herbivore‐mediated nutrient recycling may lower the probability of consistent interactive effects on producer biomass. Continuing studies should expand the temporal and spatial scales of experiments, particularly in understudied terrestrial systems; broaden factorial designs to manipulate independently multiple producer resources (e.g. nitrogen, phosphorus, light), multiple herbivore taxa or guilds (e.g. vertebrates and invertebrates) and multiple trophic levels; and – in addition to measuring producer biomass – assess the responses of species diversity, community composition and nutrient status.

Landscape characteristics influence morphological and genetic differentiation in a widespread raptor ( Buteo jamaicensis ) - JOSHUA M. HULL; ANGUS C. HULL; BENJAMIN N. SACKS; JEFF P. SMITH; HOLLY B. ERNEST (Molecular Ecology, 2008)
Landscape‐scale population genetic structure in vagile vertebrates was commonly considered to be a contradiction in terms whereas recent studies have demonstrated behaviour and habitat associated structure in several such species. We investigate whether landscape features influence morphological and genetic differentiation in a widespread, mobile raptor. To accurately describe genetic differentiation associated with regional landscape factors, we first investigated subspecies relationships at a continental scale. We used 17 microsatellite loci and five morphological measurements to investigate differentiation between eastern and western subspecies of red‐tailed hawks ( Buteo jamaicensis ) and to identify patterns between differentiation and habitat within western North America. Bayesian and frequency‐based analyses of microsatellite data revealed clear distinctions between B. j. borealis (eastern) and B. j. calurus (western) samples. Furthermore, hawks sampled in Texas were stouter than those collected from the Rocky Mountains and farther west. Among western samples, birds from the Great Basin, Rocky Mountains, and Washington were significantly different in morphology than those from Oregon and California. We identified a pattern of isolation by distance among western breeding sites around the Sierra Nevada. Given the long‐range dispersal capabilities of raptors, this pattern suggests that population‐specific habitat preferences, corresponding with habitat breaks between eastern and western slopes of the Sierra Nevada, and/or regionally variable population densities limit migration between the Mediterranean habitat of central California and the xeric habitats of southern California and interior west. We suggest habitat preferences and regionally disparate population densities may play a role in shaping genetic structure in vagile avian taxa.

Gauge repeatability and reproducibility for accessing variability during dissolution testing: A technical note - Zongming Gao; Terry Moore; Anjanette P. Smith; William Doub; Benjamin Westenberger; Lucinda Buhse (AAPS PharmSciTech, 2007)

Projected Changes in Terrestrial Carbon Storage in Europe under Climate and Land-use Change, 1990–2100 - Sönke Zaehle; Alberte Bondeau; Timothy R. Carter; Wolfgang Cramer; Markus Erhard; I. Colin Prentice; I. Reginster; Mark D. A. Rounsevell; Stephen Sitch; Benjamin Smith; Pascalle C. Smith; Martin Sykes (Ecosystems, 2007)

Modelling the role of agriculture for the 20th century global terrestrial carbon balance - ALBERTE BONDEAU; PASCALLE C. SMITH; SÖNKE ZAEHLE; SIBYLL SCHAPHOFF; WOLFGANG LUCHT; WOLFGANG CRAMER; DIETER GERTEN; HERMANN LOTZE‐CAMPEN; CHRISTOPH MÜLLER; MARKUS REICHSTEIN; BENJAMIN SMITH (Global Change Biology, 2007)
In order to better assess the role of agriculture within the global climate‐vegetation system, we present a model of the managed planetary land surface, Lund–Potsdam–Jena managed Land (LPJmL), which simulates biophysical and biogeochemical processes as well as productivity and yield of the most important crops worldwide, using a concept of crop functional types (CFTs). Based on the LPJ‐Dynamic Global Vegetation Model, LPJmL simulates the transient changes in carbon and water cycles due to land use, the specific phenology and seasonal CO 2 fluxes of agricultural‐dominated areas, and the production of crops and grazing land. It uses 13 CFTs (11 arable crops and two managed grass types), with specific parameterizations of phenology connected to leaf area development. Carbon is allocated daily towards four carbon pools, one being the yield‐bearing storage organs. Management (irrigation, treatment of residues, intercropping) can be considered in order to capture their effect on productivity, on soil organic carbon and on carbon extracted from the ecosystem. For transient simulations for the 20th century, a global historical land use data set was developed, providing the annual cover fraction of the 13 CFTs, rain‐fed and/or irrigated, within 0.5° grid cells for the period 1901–2000, using published data on land use, crop distributions and irrigated areas. Several key results are compared with observations. The simulated spatial distribution of sowing dates for temperate cereals is comparable with the reported crop calendars. The simulated seasonal canopy development agrees better with satellite observations when actual cropland distribution is taken into account. Simulated yields for temperate cereals and maize compare well with FAO statistics. Monthly carbon fluxes measured at three agricultural sites also compare well with simulations. Global simulations indicate a ∼24% (respectively ∼10%) reduction in global vegetation (respectively soil) carbon due to agriculture, and 6–9 Pg C of yearly harvested biomass in the 1990s. In contrast to simulations of the potential natural vegetation showing the land biosphere to be an increasing carbon sink during the 20th century, LPJmL simulates a net carbon source until the 1970s (due to land use), and a small sink (mostly due to changing climate and CO 2 ) after 1970. This is comparable with earlier LPJ simulations using a more simple land use scheme, and within the uncertainty range of estimates in the 1980s and 1990s. The fluxes attributed to land use change compare well with Houghton's estimates on the land use related fluxes until the 1970s, but then they begin to diverge, probably due to the different rates of deforestation considered. The simulated impacts of agriculture on the global water cycle for the 1990s are∼5% (respectively∼20%) reduction in transpiration (respectively interception), and∼44% increase in evaporation. Global runoff, which includes a simple irrigation scheme, is practically not affected.

Changes in European ecosystem productivity and carbon balance driven by regional climate model output - PABLO MORALES; THOMAS HICKLER; DAVID P. ROWELL; BENJAMIN SMITH; MARTIN T. SYKES (Global Change Biology, 2007)
Climate change resulting from the enhanced greenhouse effect together with the direct effect of increased atmospheric CO 2 concentrations on vegetation growth are expected to produce changes in the cycling of carbon in terrestrial ecosystems. Impacts will vary across Europe, and regional‐scale studies are needed to resolve this variability. In this study, we used the LPJ‐GUESS ecosystem model driven by a suite of regional climate model (RCM) scenarios from the European Union (EU) project PRUDENCE to estimate climate impacts on carbon cycling across Europe. We identified similarities and discrepancies in simulated climate impacts across scenarios, particularly analyzing the uncertainties arising from the range of climate models and emissions scenarios considered. Our results suggest that net primary production (NPP) and heterotrophic respiration (Rh) will generally increase throughout Europe, but with considerable variation between European subregions. The smallest NPP increases, and in some cases decreases, occurred in the Mediterranean, where many ecosystems switched from sinks to sources of carbon by 2100, mainly as a result of deteriorating water balance. Over the period 1991–2100, modeled climate change impacts on the European carbon balance ranged from a sink of 11.6 Gt C to a source of 3.3 Gt C, the average annual sink corresponding with 1.85% of the current EU anthropogenic emissions. Projected changes in carbon balance were more dependent on the choice of the general circulation model (GCM) providing boundary conditions to the RCM than the choice of RCM or the level of anthropogenic greenhouse gases emissions.

Biocolloid retention in partially saturated soils - Tammo S. Steenhuis; Annette Dathe; Yuniati Zevi; Jennifer L. Smith; Bin Gao; Stephen B. Shaw; Dilkushi DeAlwis; Samary Amaro-Garcia; Rosemarie Fehrman; M. Ekrem Cakmak; Ian C. Toevs; Benjamin M. Liu; et al. (Biologia, 2006)

Implementing plant hydraulic architecture within the LPJ Dynamic Global Vegetation Model - Thomas Hickler; I. Colin Prentice; Benjamin Smith; Martin T. Sykes; Sönke Zaehle (Global Ecology and Biogeography, 2006)
Aim To implement plant hydraulic architecture within the Lund–Potsdam–Jena Dynamic Global Vegetation Model (LPJ–DGVM), and to test the model against a set of observational data. If the model can reproduce major patterns in vegetation and ecosystem processes, we consider this to be an important linkage between plant physiology and larger‐scale ecosystem dynamics. Location The location is global, geographically distributed. Methods A literature review was carried out to derive model formulations and parameter values for representing the hydraulic characteristics of major global plant functional types (PFTs) in a DGVM. After implementing the corresponding formulations within the LPJ–DGVM, present‐day model output was compared to observational data. Results The model reproduced observed broad‐scale patterns in potential natural vegetation, but it failed to distinguish accurately between different types of grassland and savanna vegetation, possibly related to inadequate model representations of water fluxes in the soil and wildfire effects. Compared to a version of the model using an empirical formulation for calculating plant water supply without considering plant hydraulic architecture, the new formulation improved simulated patterns of vegetation in particular for dry shrublands. Global‐scale simulation results for runoff and actual evapotranspiration (AET) corresponded well to available data. The model also successfully reproduced the magnitude and seasonal cycle of AET for most EUROFLUX forests, while modelled variation in NPP across a large number of sites spanning several biomes showed a strong correlation with estimates from field measurements. Main conclusions The model was generally confirmed by comparison to observational data. The novel model representation of water flow within plants makes it possible to resolve mechanistically the effects of hydraulic differences between plant functional groups on vegetation structure, water cycling, and competition. This may be an advantage when predicting ecosystem responses to nonextant climates, in particular in areas dominated by dry shrubland vegetation.

Modelling Regional Climate Change Effects On Potential Natural Ecosystems in Sweden - Deniz Koca; Benjamin Smith; Martin T. Sykes (Climatic Change, 2006)

Implementing plant hydraulic architecture within the LPJ Dynamic Global Vegetation Model - Thomas Hickler; I. Colin Prentice; Benjamin Smith; Martin T. Sykes; Sonke Zaehle (Global Ecology and Biogeography, 2006)

Europe's 2003 heat wave: a satellite view of impacts and land–atmosphere feedbacks - Benjamin F. Zaitchik; Alison K. Macalady; Laurent R. Bonneau; Ronald B. Smith (International Journal of Climatology, 2006)
A combination of satellite imagery, meteorological station data, and the NCEP/NCAR reanalysis has been used to explore the spatial and temporal evolution of the 2003 heat wave in France, with focus on understanding the impacts and feedbacks at the land surface. Vegetation was severely affected across the study area, especially in a swath across central France that corresponds to the Western European Broadleaf (WEB) Forests ecological zone. The remotely sensed surface temperature anomaly was also greatest in this zone, peaking at +15.4 °C in August. On a finer spatial scale, both the vegetation and surface temperature anomalies were greater for crops and pastures than for forested lands. The heat wave was also associated with an anomalous surface forcing of air temperature. Relative to other years in record, satellite‐derived estimates of surface‐sensible heat flux indicate an enhancement of 48–61% (24.0–30.5 W m −2 ) in WEB during the August heat wave maximum. Longwave radiative heating of the planetary boundary layer (PBL) was enhanced by 10.5 W m −2 in WEB for the same period. The magnitude and spatial structure of this local heating is consistent with models of the late twenty‐first century climate in France, which predict a transitional climate zone that will become increasingly affected by summertime drought. Models of future climate also suggest that a soil‐moisture feedback on the surface energy balance might exacerbate summertime drought, and these proposed feedback mechanisms were tested using satellite‐derived heat budgets. Copyright © 2006 Royal Meteorological Society.

Sensitivity of African biomes to changes in the precipitation regime - Christelle Hely; Laurent Bremond; Samuel Alleaume; Benjamin Smith; Martin T. Sykes; Joel Guiot (Global Ecology and Biogeography, 2006)

Sensitivity of African biomes to changes in the precipitation regime - Christelle Hély; Laurent Bremond; Samuel Alleaume; Benjamin Smith; Martin T. Sykes; Joël Guiot (Global Ecology and Biogeography, 2006)
Aim Africa is identified by the Inter‐governmental Panel on Climate Change (IPCC) as the least studied continent in terms of ecosystem dynamics and climate variability. The aim of this study was (1) to adapt the Lund‐Postdam‐Jena‐GUESS (LPJ‐GUESS) ecological modelling framework to Africa by providing new parameter values for tropical plant functional types (PFT), and (2) to assess the sensitivity of some African biomes to changes in precipitation regime. Location The study area was a representative transect (0–22° N and 7–18° E) through the transition from equatorial evergreen forests to savannas, steppes and desert northwards. The transect showed large latitudinal variation in precipitation (mean rainfall ranged from 50 to 2300 mm year −1 ). Methods New PFT parameters used to calibrate LPJ‐GUESS were based on modern pollen PFTs and remote sensed leaf area index (LAI). The model was validated using independent modern pollen assemblages, LAI and through comparison with White's modern potential vegetation map. Several scenarios were developed by combining changes in total rainfall amount with variation in the length of the dry season in order to test the sensitivity of African biomes. Results Simulated vegetation compared well to observed data at local and regional scales, in terms of ecosystem functioning (LAI), and composition (pollen and White's vegetation map). The assessment of the sensitivity of biomes to changes in precipitation showed that none of the ecosystems would shift towards a new type under the range of precipitation increases suggested by the IPCC (increases from 5 to 20%). However, deciduous and semi‐deciduous forests may be very sensitive to small reductions in both the amount and seasonality of precipitation. Main conclusions This version of LPJ‐GUESS parameterized for Africa simulated correctly the vegetation present over a wide precipitation gradient. The biome sensitivity assessment showed that, compared with savannas and grasslands, closed canopy forests may be more sensitive to change in precipitation regime due to the synergetic effects of changed rainfall amounts and seasonality on vegetation functioning.

Comparing and evaluating process‐based ecosystem model predictions of carbon and water fluxes in major European forest biomes - Pablo Morales; Martin T. Sykes; I. Colin Prentice; Pete Smith; Benjamin Smith; Harald Bugmann; Bärbel Zierl; Pierre Friedlingstein; Nicolas Viovy; Santi Sabaté; Anabel Sánchez; Eduard Pla; et al. (Global Change Biology, 2005)
Process‐based models can be classified into: (a) terrestrial biogeochemical models (TBMs), which simulate fluxes of carbon, water and nitrogen coupled within terrestrial ecosystems, and (b) dynamic global vegetation models (DGVMs), which further couple these processes interactively with changes in slow ecosystem processes depending on resource competition, establishment, growth and mortality of different vegetation types. In this study, four models – RHESSys, GOTILWA+, LPJ‐GUESS and ORCHIDEE – representing both modelling approaches were compared and evaluated against benchmarks provided by eddy‐covariance measurements of carbon and water fluxes at 15 forest sites within the EUROFLUX project. Overall, model‐measurement agreement varied greatly among sites. Both modelling approaches have somewhat different strengths, but there was no model among those tested that universally performed well on the two variables evaluated. Small biases and errors suggest that ORCHIDEE and GOTILWA+ performed better in simulating carbon fluxes while LPJ‐GUESS and RHESSys did a better job in simulating water fluxes. In general, the models can be considered as useful tools for studies of climate change impacts on carbon and water cycling in forests. However, the various sources of variation among models simulations and between models simulations and observed data described in this study place some constraints on the results and to some extent reduce their reliability. For example, at most sites in the Mediterranean region all models generally performed poorly most likely because of problems in the representation of water stress effects on both carbon uptake by photosynthesis and carbon release by heterotrophic respiration ( R h ). The use of flux data as a means of assessing key processes in models of this type is an important approach to improving model performance. Our results show that the models have value but that further model development is necessary with regard to the representation of the some of the key ecosystem processes.

Serotonin transport kinetics correlated between human platelets and brain synaptosomes - Jeffrey L. Rausch; Maria E. Johnson; Junqing Li; Julian Hutcheson; Benjamin M. Carr; Katina M. Corley; Amanda B. Gowans; Joseph Smith (Psychopharmacology, 2005)

The North Atlantic Oscillation and regional phenology prediction over Europe - Benjamin I. Cook; Thomas M. Smith; Michael E. Mann (Global Change Biology, 2005)
We present an integrated modeling study designed to investigate changes in ecosystem level phenology over Europe associated with changes in climate pattern, by the North Atlantic Oscillation (NAO). We derived onset dates from processed NDVI data sets and used growing degree day (GDD) summations from the NCEP re‐analysis to calibrate and validate a phenology model to predict the onset of the growing season over Europe. In a cross‐validation hindcast, the model (PHENOM) is able to explain 63% of the variance in onset date for grid cells containing at least 50% mixed and boreal forest. Using a model developed from previous work we performed climate change scenarios, generating synthetic temperature and GDD distributions under a hypothetically increasing NAO. These new distributions were used to drive PHENOM and project changes in the timing of onset for forested cells over Europe. Results from the climate change scenarios indicate that, if the current trend in the NAO continues, there is the potential for a continued advance to the start of the growing season by as much as 13 days in some areas.

Chemical and Olfactory Characterization of Odorous Compounds and Their Precursors in the Parotoid Gland Secretion of the Green Tree Frog, Litoria caerulea - Benjamin P. C. Smith; Michael J. Tyler; Brian D. Williams; Yoji Hayasaka (Journal of Chemical Ecology, 2003)

Intraspecific Variation in Odor-Mediated Host Preference of the Mosquito Culex annulirostris - Craig R. Williams; Michael J. Kokkinn; Benjamin P. Smith (Journal of Chemical Ecology, 2003)

Genetic linkage of Francois-Neetens fleck (mouchetée) corneal dystrophy to chromosome 2q35 - Xiaodong Jiao; Francis L. Munier; Daniel F. Schorderet; Leonidas Zografos; Janine Smith; Benjamin Rubin; J. Fielding Hejtmancik (Human Genetics, 2003)

Regeneration in Gap Models: Priority Issues for Studying Forest Responses to Climate Change - David T. Price; Niklaus E. Zimmermann; Peter J. van der Meer; Manfred J. Lexer; Paul Leadley; Irma T. M. Jorritsma; Jörg Schaber; Donald F. Clark; Petra Lasch; Steve McNulty; Jianguo Wu; Benjamin Smith (Climatic Change, 2001)

Tree Species Composition in European Pristine Forests: Comparison of Stand Data to Model Predictions - Franz-W. Badeck; Heike Lischke; Harald Bugmann; Thomas Hickler; Karl Hönninger; Petra Lasch; Manfred J. Lexer; Florent Mouillot; Jörg Schaber; Benjamin Smith (Climatic Change, 2001)

Representation of vegetation dynamics in the modelling of terrestrial ecosystems: comparing two contrasting approaches within European climate space - Benjamin Smith; I. Colin Prentice; Martin T. Sykes (Global Ecology and Biogeography, 2001)
Advances in dynamic ecosystem modelling have made a number of different approaches to vegetation dynamics possible. Here we compare two models representing contrasting degrees of abstraction of the processes governing dynamics in real vegetation. Model (a) (GUESS) simulates explicitly growth and competition among individual plants. Differences in crown structure (height, depth, area and LAI) influence relative light uptake by neighbours. Assimilated carbon is allocated individually by each plant to its leaf, fine root and sapwood tissues. Carbon allocation and turnover of sapwood to heartwood in turn govern height and diameter growth. Model (b) (LPJ) incorporates a ‘dynamic global vegetation model’ (DGVM) architecture, simulating growth of populations of plant functional types (PFTs) over a grid cell, integrating individual‐level processes over the proportional area (foliar projective cover, FPC) occupied by each PFT. Individual plants are not simulated, but are replaced by explicit parameterizations of their growth and interactions. The models are identical in their representation of core physiological and biogeochemical processes. Both also use the same set of PFTs, corresponding to the major woody plant groups in Europe, plus a grass type. When applied at a range of locations, broadly spanning climatic variation within Europe, both models successfully predicted PFT composition and succession within modern natural vegetation. However, the individual‐based model performed better in areas where deciduous and evergreen types coincide, and in areas subject to pronounced seasonal water deficits, which would tend to favour grasses over drought‐intolerant trees. Differences in model performance could be traced to their treatment of individual‐level processes, in particular light competition and stress‐induced mortality. Our results suggest that an explicit individual‐based approach to vegetation dynamics may be an advantage in modelling of ecosystem structure and function at the resolution required for regional‐ to continental‐scale studies.

An introduction to the European Terrestrial Ecosystem Modelling Activity - Martin T. Sykes; I. Colin Prentice; Benjamin Smith; Wolfgang Cramer; Sergey Venevsky (Global Ecology and Biogeography, 2001)
The objective of the European Terrestrial Ecosystem Modelling Activity (ETEMA) was to address some of the major challenges in developing generalized models to examine responses of natural and seminatural ecosystems to environmental change at the regional to European scale. The approach described herein was to break down the totality of ecosystem functioning into its key components, each with its characteristic spatial and temporal scales. A conceptual framework was developed describing the configuration of these components as modules within a generalized simulation model. The framework describes the key inputs, outputs and state variables, their spatial and temporal contexts, and information flows between modules. The ‘backbone’ of the model is a system of nested timing loops corresponding to the disparate time scales at which different ecosystem processes occur. The framework is a theoretical construct into which ecosystem models at levels of complexity ranging from the very general to the highly detailed can be mapped, and thus provides a guide for development of models for novel, particularly regional‐scale, applications. A number of subsystem studies of the major components of ecosystem functioning, i.e. modules of the conceptual framework, are briefly introduced herein. The general aim of the subsystem studies was to identify the key alternative formulations (as opposed to minor variants) and test these against observational data. The various subsystem studies concern planetary boundary layer–ecosystem interactions, ecosystem CO 2 and H 2 O fluxes, vegetation physiology and phenology, biogeography and vegetation dynamics, detritus and SOM dynamics, soil moisture and human and natural disturbances and, as individual papers, they complete this special ETEMA issue.

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Life-history studies of Lydella jalisco (Diptera: Tachinidae), a parasitoid of Eoreuma loftini (Lepidoptera: Pyralidae) - Isabelle Lauziere; Jesusa C. Legaspi; Benjamin C. Legaspi; James W. Smith; Walker A. Jones (BioControl, 2001)